Magnetic recording medium, magnetic tape cartridge, and magnetic recording and reproducing device
Patent Information
- Application Number
- JP2023140627
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-13
AI Technical Summary
【0008】 本発明の一態様によれば、繰り返し走行後に低摩擦係数を示すことができる磁気記録媒体を提供することができる。また、本発明の一態様によれば、上記磁気記録媒体を含む磁気テープカートリッジおよび磁気記録再生装置を提供することができる。
Smart Images

Figure 2025034317000001 
Figure 2025034317000002 
Figure 2025034317000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a magnetic recording medium, a magnetic tape cartridge, and a magnetic recording / reproducing device. [Background technology]
[0002] Magnetic recording media are generally produced by forming a magnetic layer containing ferromagnetic powder on a non-magnetic support (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 4070147 specification [Patent Document 2] Japanese Patent Application Publication No. 10-261220 Summary of the Invention [Problem to be solved by the invention]
[0004] Recording data on a magnetic recording medium and reproducing the recorded data are usually performed by running the magnetic recording medium in a magnetic recording and reproducing device and bringing the magnetic layer surface of the magnetic recording medium into contact with a magnetic head and sliding them. From the viewpoint of running stability, it is desirable that the coefficient of friction during sliding between the magnetic layer surface and the magnetic head is low even when the magnetic recording medium is repeatedly run.
[0005] An object of one aspect of the present invention is to provide a magnetic recording medium that can exhibit a low coefficient of friction even after repeated running. [Means for solving the problem]
[0006] Patent Document 1 and Patent Document 2 disclose the addition of a silicon (Si)-containing compound to the magnetic layer (see claim 1 of Patent Document 1 and Patent Document 2, etc.). In response to this, the present inventors conducted extensive research to provide a magnetic recording medium that can exhibit a low friction coefficient even after repeated running, and as a result, discovered the following "-O-SiR 11 R 12 R 13 " is a monovalent substituent represented by the linking group L 11 It has been newly discovered that a magnetic recording medium containing a silicon-containing compound having a branched structure in which two or more silicon atoms are bonded to a non-magnetic support on the magnetic layer side (details will be described later) can exhibit a low friction coefficient after repeated running.
[0007] That is, one aspect of the present invention is as follows. [1] A magnetic recording medium having a non-magnetic support and a magnetic layer containing a ferromagnetic powder, The non-magnetic support contains a silicon-containing compound having a partial structure represented by the following formula 1 (hereinafter, simply referred to as "silicon-containing compound") on the magnetic layer side thereof, [ka] In formula 1, R 11 , R 12 and R 13 each independently represents a monovalent substituent; L 11 represents a (n+1)-valent linking group, n represents an integer of 2 or more, and * represents the position at which the partial structure represented by formula 1 is bonded to another partial structure that constitutes the silicon-containing compound. [2] The silicon-containing compound is a polymer having a structural unit represented by the following formula 2: [ka] In formula 2, R 21 and R 22 each independently represents a hydrogen atom or an alkyl group; R 23 represents a hydrogen atom or a monovalent substituent, L 12represents a single bond or a divalent linking group, * represents the position at which the structural unit represented by formula 2 is bonded to another partial structure constituting the silicon-containing compound, R 11 , R 12 , R 13 , L 11 and n are R in formula 1, 11 , R 12 , R 13 , L 11 and n is synonymous with n. [3] In formula 2, R 21 and R 22 represents a hydrogen atom, and R 23 represents a hydrogen atom or a methyl group. [4] The constitutional unit represented by formula 2 is a constitutional unit represented by the following formula 3: [ka] In formula 3, R 23 represents a hydrogen atom or a methyl group, * represents the position at which the structural unit represented by formula 3 is bonded to other partial structures constituting the silicon-containing compound, R 11 , R 12 , R 13 , L 11 and n are R in formula 1, 11 , R 12 , R 13 , L 11 and n is synonymous with n. [5] The magnetic recording medium according to any one of [2] to [4], wherein the polymer contains at least one selected from the group consisting of a carboxy group, an amino group, a hydroxy group, a sulfo group, a phosphonoxy group and salts thereof, an alkyl group, a glycol structure, an ester structure, an amide structure, an anionic structure, and an amphoteric structure. [6] The magnetic recording medium according to any one of [2] to [4], wherein the polymer contains at least one selected from the group consisting of a carboxy group, an amino group, a hydroxy group, a sulfo group, a phosphonoxy group and salts thereof, an alkyl group, and a glycol structure. [7] The magnetic recording medium according to any one of [2] to [4], wherein the polymer contains at least one selected from the group consisting of a carboxy group, an amino group, a hydroxy group, a sulfo group, a phosphonoxy group, and salts thereof, an ester structure, and an amide structure. [8] The magnetic recording medium according to any one of [2] to [7], wherein the weight average molecular weight of the polymer is 2,000 or more and less than 200,000. [9] The polymer contains at least one selected from the group consisting of a carboxy group, an amino group, a hydroxy group, a sulfo group, a phosphonoxy group, and salts thereof, an ester structure, and an amide structure; and The magnetic recording medium according to [4], wherein the weight average molecular weight of the polymer is 2,000 or more and less than 200,000.
[10] The magnetic recording medium according to [1], wherein the silicon-containing compound is a nitrogen-containing polymer.
[11] The magnetic recording medium according to
[10] , wherein the nitrogen-containing polymer is a polyalkyleneimine-based polymer.
[12] The magnetic recording medium according to
[10] or
[11] , wherein the nitrogen-containing polymer further has a polyester chain.
[13] The magnetic recording medium according to any one of
[10] to
[12] , wherein the nitrogen-containing polymer has a weight average molecular weight of 4,000 or more and less than 20,000.
[14] The nitrogen-containing polymer is a polyalkyleneimine-based polymer, The polyalkyleneimine-based polymer further has a polyester chain, and The magnetic recording medium according to
[10] , wherein the polyalkyleneimine polymer has a weight average molecular weight of 4,000 or more and less than 20,000.
[15] The magnetic recording medium according to any one of [1] to
[14] , wherein the contact angle with water (also simply referred to as "contact angle") measured on the surface of the magnetic layer is 90° or greater.
[16] The magnetic recording medium according to any one of [1] to
[15] , further comprising at least one fatty acid compound selected from the group consisting of fatty acids, fatty acid esters, and fatty acid amides, on the magnetic layer side of the non-magnetic support.
[17] The magnetic recording medium according to any one of [1] to
[16] , further comprising a non-magnetic layer containing non-magnetic powder between the non-magnetic support and the magnetic layer.
[18] The magnetic recording medium according to any one of [1] to
[17] , further comprising a backcoat layer containing a nonmagnetic powder on the surface side of the nonmagnetic support opposite to the surface side having the magnetic layer.
[19] The magnetic recording medium according to any one of [1] to
[18] , which is a magnetic tape.
[20] The contact angle with water measured on the surface of the magnetic layer is 90° or more; the non-magnetic support further contains at least one fatty acid compound selected from the group consisting of fatty acids, fatty acid esters, and fatty acid amides in the portion on the magnetic layer side of the non-magnetic support, a non-magnetic layer containing a non-magnetic powder between the non-magnetic support and the magnetic layer, a backcoat layer containing a nonmagnetic powder on the surface side of the nonmagnetic support opposite to the surface side having the magnetic layer; and The magnetic recording medium according to [9], which is a magnetic tape.
[21] The contact angle with water measured on the surface of the magnetic layer is 90° or more; the non-magnetic support further contains at least one fatty acid compound selected from the group consisting of fatty acids, fatty acid esters, and fatty acid amides in the portion on the magnetic layer side of the non-magnetic support, a non-magnetic layer containing a non-magnetic powder between the non-magnetic support and the magnetic layer, a backcoat layer containing a nonmagnetic powder on the surface side of the nonmagnetic support opposite to the surface side having the magnetic layer; and The magnetic recording medium according to
[14] , which is a magnetic tape.
[22] A magnetic tape cartridge comprising the magnetic tape according to any one of
[19] to
[21] .
[23] A magnetic recording and reproducing device comprising the magnetic recording medium according to any one of [1] to
[21] . Effect of the Invention
[0008] According to one aspect of the present invention, it is possible to provide a magnetic recording medium that exhibits a low coefficient of friction after repeated running. Also, according to one aspect of the present invention, it is possible to provide a magnetic tape cartridge and a magnetic recording and reproducing device that include the magnetic recording medium. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] [Magnetic recording media] One aspect of the present invention relates to a magnetic recording medium having a non-magnetic support and a magnetic layer containing a ferromagnetic powder, the magnetic recording medium including a silicon-containing compound having a partial structure represented by formula 1 in a portion of the non-magnetic support facing the magnetic layer.
[0010] In the present invention and this specification, the "portion on the non-magnetic support facing the magnetic layer" refers to the magnetic layer in the case of a magnetic recording medium having a magnetic layer directly on the non-magnetic support, and refers to the magnetic layer and / or the non-magnetic layer in the case of a magnetic recording medium having a non-magnetic layer described below between the non-magnetic support and the magnetic layer. The "portion on the non-magnetic support facing the magnetic layer" is also simply referred to as the "portion on the magnetic layer side." The presence of a certain component on the surface facing the magnetic layer of the magnetic recording medium is also included in the component being included in the portion on the magnetic layer side.
[0011] The magnetic recording medium includes a silicon-containing compound having a partial structure represented by formula 1 in the magnetic layer side portion. It is believed that the silicon-containing compound can function as a lubricant for the magnetic recording medium. The inventor believes that the silicon-containing compound can function as a lubricant for the magnetic recording medium to provide lubricity to the magnetic layer surface, which contributes to the magnetic recording medium being able to exhibit a low friction coefficient after repeated running. For example, it is believed that at least a part of the silicon-containing compound contained in the magnetic layer can be present on the magnetic layer surface. Furthermore, the inventor presumes that the silicon-containing compound contained inside the magnetic layer can be present on the magnetic layer surface by moving to the magnetic layer surface during sliding with the magnetic head, etc. In addition, the silicon-containing compound may be contained in the non-magnetic layer described later, and it is believed that the silicon-containing compound contained in the non-magnetic layer can move to the magnetic layer and further move to the magnetic layer surface to be present on the magnetic layer surface. Furthermore, the present inventors believe that the inclusion of a silicon-containing compound having a partial structure represented by formula 1 in the magnetic layer side portion of the magnetic recording medium may also contribute to reducing changes in the surface shape of the magnetic layer before and after repeated running. Minimizing changes in the surface shape of the magnetic layer before and after repeated running is desirable from the viewpoint of preventing deterioration in the performance of the magnetic recording medium after repeated running. However, the above is merely speculation and does not limit the present invention, nor is the present invention limited to other speculations described in this specification.
[0012] The above magnetic recording medium will now be described in more detail.
[0013] <Silicon-containing compounds> The silicon-containing compound includes a silicon-containing compound having a partial structure represented by the following formula 1. 11 R 12 R 13 " is a monovalent substituent represented by the linking group L 1The present inventors speculate that the silicon-containing branched structure having two or more bonds to the silicon-containing compound contributes to the magnetic recording medium containing the silicon-containing compound in the magnetic layer side portion exhibiting a low friction coefficient after repeated running, and further contributes to reducing the change in the surface shape of the magnetic layer before and after repeated running. In one embodiment, the silicon-containing compound can be a compound that does not contain a fluorine atom as an atom that constitutes the compound.
[0014] [ka]
[0015] The silicon compound will be described in more detail below. In the present invention and this specification, unless otherwise specified, the groups described may be unsubstituted or may have a substituent. When a group has a substituent, examples of the substituent include an alkyl group (e.g., an alkyl group having 1 to 6 carbon atoms), a hydroxyl group, an alkoxy group (e.g., an alkoxy group having 1 to 6 carbon atoms), a cyano group, an amino group, a nitro group, an acyl group, and a carboxyl group. In addition, the "carbon number" of a group having a substituent means the carbon number of the portion not including the substituent. In addition, in the present invention and this specification, unless otherwise specified, the "alkyl group", "alkylene group", "alkenyl group" and "hydrocarbon group" each include the linear, branched and cyclic forms of each group.
[0016] In formula 1, R 11 , R 12 and R 13 each independently represents a monovalent substituent; L 11 represents a (n+1)-valent linking group, n represents an integer of 2 or more, and * represents the position at which the partial structure represented by formula 1 is bonded to another partial structure constituting the silicon-containing compound. In the present invention and this specification, * represents the position at which partial structures are bonded to each other, and the notation * may be omitted in some cases.
[0017] In formula 1, R 11 , R 12 and R 13may be the same or different. In addition, when there are two or more R 11 may be the same or different. In this respect, R 12 and R 13 The same applies to.
[0018] R 11 , R 12 and R 13 can each independently represent an alkyl group, an alkenyl group, an aryl group, or an alkylenearyl group, and is preferably an alkyl group or an aryl group.
[0019] Examples of the alkyl group include a linear alkyl group having 1 to 18 carbon atoms, a branched alkyl group having 3 to 18 carbon atoms, and a cyclic alkyl group having 3 to 18 carbon atoms. Specific examples of the alkyl group include a methyl group, an ethyl group, a propyl group, a butyl group, an isopropyl group, a tert(tertiary)-butyl group, and a cyclohexyl group.
[0020] Examples of the alkenyl group include alkenyl groups having a carbon number of 2 to 12. Specific examples of the alkenyl group include a vinyl group, a 1-propenyl group, a 1-butenyl group, a 1-methyl-1-propenyl group, a 1-cyclopentenyl group, and a 1-cyclohexenyl group.
[0021] The aryl group may, for example, be an aryl group having a carbon number of 6 to 12. Specific examples of the aryl group include a phenyl group, an α-methylphenyl group, and a naphthyl group.
[0022] The alkylenearyl group may, for example, be an alkylenearyl group having 7 to 30 carbon atoms.
[0023] In formula 1, R 11 , R 12 , and R 13are preferably each independently an alkyl group, more preferably all the same alkyl group, even more preferably all the same alkyl group having 1 to 4 carbon atoms, and even more preferably all methyl groups.
[0024] In formula 1, n represents an integer of 2 or more, and preferably represents an integer of 3 or more. n can be, for example, 12 or less, 11 or less, 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, or 4 or less.
[0025] In formula 1, L 11 Examples of the (n+1)-valent linking group represented by the formula (1) include a (n+1)-valent linear or branched hydrocarbon group having 1 to 10 carbon atoms, and a hydrocarbon group in which a part of the carbon atoms constituting the (n+1)-valent linear or branched hydrocarbon group is substituted with a hetero atom. Examples of the hetero atom substituting a part of the carbon atom include a silicon atom, an oxygen atom, and a nitrogen atom, and among these, a silicon atom or an oxygen atom is preferred, and a silicon atom is more preferred. The above-mentioned hydrocarbon group can be a saturated hydrocarbon group or an unsaturated hydrocarbon group, and is preferably a saturated hydrocarbon group.
[0026] In one form, L 11 The (n+1)-valent linking group represented by the formula (I) may be a linear or branched alkylene group having 1 to 10 carbon atoms, or may be a substituted alkylene group in which some of the carbon atoms constituting the linear or branched alkylene group having 1 to 10 carbon atoms are substituted with heteroatoms. For example, L 11 may be a tetravalent linking group in which a silicon atom is bonded to the end of a linear alkylene group having 1 to 10 carbon atoms. 11 In the case where R has the formula, the partial structure represented by formula 1 can be represented by the following formula 1-1. In formula 1-1, m represents an integer of 1 or more and 10 or less. m can also be 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, or 4 or less. 41 , R 42 and R 43 , R 51 , R 52 and R53 , R 61 , R 62 and R 63 are R in Eq. 11 , R 12 and R 13 The symbol * in formula 1-1 has the same meaning as the symbol * in formula 1, and the details are as described above. [ka]
[0027] The magnetic recording medium may contain only one of the silicon-containing compounds in the magnetic layer, or may contain two or more of the silicon-containing compounds with different structures. The silicon-containing compound may be a polymer having a structural unit represented by the following formula 2 in one embodiment, or a nitrogen-containing polymer in another embodiment. In the present invention and this specification, the term "polymer" includes homopolymers and copolymers.
[0028] Each of the above polymers will now be described in more detail.
[0029] (1) Polymer having a structural unit represented by formula 2
[0030] In one embodiment, the silicon-containing compound can be a polymer having constitutional units represented by formula 2. [ka]
[0031] In formula 2, R 21 and R 22 each independently represents a hydrogen atom or an alkyl group; R 23 represents a hydrogen atom or a monovalent substituent.
[0032] R 21 and R 22 In one embodiment, each of R represents a hydrogen atom, and in another embodiment, one of R represents a hydrogen atom and the other represents an alkyl group.21 and R 22 R represents the same or different alkyl groups. 21 and / or R 22 For an alkyl group that can be represented by R 11 , R 12 and / or R 13 Reference can be made to the above description of alkyl groups which may be represented by:
[0033] In formula 2, R 23 R represents a hydrogen atom or a monovalent substituent. 23 Examples of monovalent substituents that can be represented by the formula (I) include alkyl groups. For such alkyl groups, R 11 , R 12 and / or R 13 Reference can be made to the above description of alkyl groups which may be represented by:
[0034] In one embodiment, in formula 2, R 21 and R 22 represents a hydrogen atom, and R 23 R represents a hydrogen atom or a methyl group. 21 and R 22 represents a hydrogen atom, and R 23 When R represents a hydrogen atom, the structural unit represented by formula 2 may be a structural unit derived from an acrylic ester. 21 and R 22 represents a hydrogen atom, and R 23 When represents a methyl group, the structural unit represented by formula 2 can be a structural unit derived from a methacrylic acid ester.
[0035] In formula 2, L 12 represents a single bond or a divalent linking group. Examples of the divalent linking group include an ester group (-C(=O)O-), a carbonyl group (-C(=O)-), and an arylene group (preferably an arylene group having 6 to 20 carbon atoms).
[0036] In formula 2, * represents the position at which the structural unit represented by formula 2 is bonded to other partial structures constituting the silicon-containing compound, and R 11 , R 12 , R 13, L 11 and n are R in formula 1, 11 , R 12 , R 13 , L 11 and n, the details of which are as described above.
[0037] In formula 2, R 21 and R 22 represents a hydrogen atom, and R 23 represents a hydrogen atom or a methyl group, and L 12 When represents an ester group, the constitutional unit represented by formula 2 can be a constitutional unit represented by formula 3 below.
[0038] [ka]
[0039] In formula 3, R 23 represents a hydrogen atom or a methyl group, * represents the position at which the structural unit represented by formula 3 is bonded to other partial structures constituting the silicon-containing compound, R 11 , R 12 , R 13 , L 11 and n are R in formula 1, 11 , R 12 , R 13 , L 11 and n, the details of which are as described above.
[0040] The polymer having the constitutional unit represented by formula 2 may be a homopolymer containing a plurality of constitutional units of the same structure represented by formula 2, or may be a copolymer containing a plurality of constitutional units of two or more different structures represented by formula 2. In such a case, in the polymer having the constitutional unit represented by formula 2, the content of the constitutional unit represented by formula 2 may be 100 mol % when the total amount of the constitutional units constituting this polymer is taken as 100 mol %. Alternatively, the polymer having the constitutional unit represented by formula 2 may be a copolymer of one or more different structural constitutional units represented by formula 2 and at least one constitutional unit other than the constitutional unit represented by formula 2. In such a case, in the polymer having the constitutional unit represented by formula 2, the content of the constitutional unit represented by formula 2 is preferably 1 mol% or more, and more preferably 10 mol% or more, 20 mol% or more, 30 mol% or more, 40 mol% or more, 50 mol% or more, 60 mol% or more, 70 mol% or more, and 80 mol% or more, in that order, when the total amount of the constitutional units constituting this polymer is 100 mol%. In addition, the content can be 99 mol% or less, 95 mol% or less, or 90 mol% or less. The content can be measured by a known method, or can be calculated from the molar ratio of the monomers used in polymer synthesis. For example, for a polymer synthesized using two types of monomers (monomers A and B) in a molar ratio of monomer A:monomer B=90:10, the content of the constituent units derived from monomer A can be calculated to be 90 mol % and the content of the constituent units derived from monomer B can be calculated to be 10 mol %, assuming that the total amount of the constituent units constituting the polymer is 100 mol %.
[0041] When the polymer having a constitutional unit represented by formula 2 is a copolymer, the copolymerization type is not particularly limited and can be any copolymerization type (for example, random copolymerization, alternating copolymerization, block copolymerization, or graft copolymerization).
[0042] In one embodiment, the polymer having a constitutional unit represented by formula 2 can contain at least one selected from the group consisting of a carboxy group (-COOH), an amino group (-NH2), a hydroxy group (-OH), a sulfo group (-S(=O)2(OH)), a phosphonoxy group (-OP(=O)(OH)2) and salts thereof, an alkyl group, a glycol structure, an ester structure, an amide structure, an anionic structure, and an amphoteric structure (also referred to as "functional group 1"). The above salts may be, for example, alkali metal salts. This also applies to salts relating to the following functional groups. For the above alkyl groups, R11 , R 12 and / or R 13 Refer to the above description regarding the alkyl group that can be represented by the following formula: This also applies to the alkyl group in the following functional groups. The glycol structures for the above glycol structures and the following functional groups include polyalkyleneoxy groups or combinations of two or more polyalkyleneoxy groups. Specific examples of the polyalkyleneoxy groups include polyethyleneoxy groups, polypropyleneoxy groups, and polybutyleneoxy groups. Examples of the above ester structure and the ester structure related to the following functional groups include carboxylate ester, sulfonate ester, phosphate ester, and boronic ester. The above amide structure and the amide structure related to the following functional group group include structures derived from acrylamides such as (meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, Nn(normal)-propyl(meth)acrylamide, N-isopropyl(meth)acrylamide, Nn-butyl(meth)acrylamide, N-methylol(meth)acrylamide, N-(2-hydroxyethyl)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, N-(2-dimethylaminoethyl)(meth)acrylamide, N-(3-dimethylaminopropyl)(meth)acrylamide, diacetone(meth)acrylamide, N,N-dimethyl(meth)acrylamide, and N-(meth)acryloylmorpholine. In the present invention and this specification, "(meth)acryl" is used to mean both acryl and methacryl. The anionic structure is "(-C(=O)-O - ) n M 1 " or "(-S(=O)2-O - ) n M 1 It is preferable that the alkyl group has a monovalent substituent represented by M 1 represents a cation, n represents a cation M 1 The above M 1is an alkali metal cation, an alkaline earth metal cation, an Mg cation, an Al cation, or an R 1 R 2 R 3 R 4 N + R can represent a quaternary ammonium cation represented by the formula: 1 ~R 4 each independently represents a hydrogen atom or a linear or branched alkyl group having 1 to 20 carbon atoms. Examples of the alkali metal include lithium (Li), sodium (Na), potassium (K), and cesium (Cs). Examples of the alkaline earth metal include calcium (Ca), strontium (Sr), and barium (Ba). The above quaternary ammonium cation (R 1 R 2 R 3 R 4 N + ) is R 1 ~R 4 are not particularly limited as long as each independently represents a hydrogen atom or a linear or branched alkyl group having 1 to 20 carbon atoms. 1 ~R 4 An example of a quaternary ammonium cation in which all the cations are the same is (CH3)4N. + , (C2H5)4N + , (C3H7)4N + , (C4H9)4N + , (C5H 11 )4N + , (CH 13 )4N + , (C7H 15 )4N + , (C8H 17 )4N + , (C9H 19 )4N + , (C 10 H 21 )4N + Also, R 1 ~R 4In the case where three of the groups represent methyl groups and the remaining group represents a linear or branched alkyl group having 1 to 20 carbon atoms other than a methyl group, the remaining group can be, for example, (C2H5), (C6H 13 ), (C8H 17 ), (C9H 19 ), (C 10 H 21 ), (C 12 H 25 ), (C 14 H 29 ), (C 16 H 33 ), (C 18 H 37 ) etc. 1 ~R 4 In the case where two of the above represent a methyl group and the other two each independently represent a linear or branched alkyl group having 1 to 20 carbon atoms other than a methyl group, for example, the other two are both (CH 17 ), (C 10 H 21 ), (C 12 H 25 ), (C 14 H 29 ), (C 16 H 33 ) or (C 18 H 37 ) can be expressed as R 1 ~R 4 In the case where one of the groups represents a methyl group and the other three groups each independently represent a linear or branched alkyl group having 1 to 20 carbon atoms other than a methyl group, for example, the other three groups are each (C4H9) or (C8H 17 ) can be represented as The amphoteric structure is preferably a "-N + R 5 R 6 R 7 ·Cl - ", -N + R 5 R 6 R 7 ·Br - ", -N + R 5 R 6 R 7 I - ", -N +R 5 R 6 R 7 CH3SO 3- ", -N + R 5 R 6 R 7 ·NO 3- ", "(-N + R 5 R 6 R 7 )2CO3 2- " or "(-N + R 5 R 6 R 7 )2SO4 2- " at the end of the R 5 ~R 7 Each of the groups independently represents a hydrogen atom or a linear or branched alkyl group having 1 to 20 carbon atoms. The amphoteric structure is a carboxybetaine type "-N + R 8 R 9 (CH2) n CO 2- " and sulfobetaine type "-N + R 8 R 9 (CH2) n SO 3- " or amine oxide type "-N + R 8 R 9 O - It is also preferable that n represents an integer ranging from 1 to 5, and R 8 and R 9 each independently represents a hydrogen atom or a linear or branched alkyl group having 1 to 10 carbon atoms.
[0043] In another embodiment, the polymer having a constitutional unit represented by formula 2 can contain at least one selected from the group consisting of a carboxy group, an amino group, a hydroxy group, a sulfo group, a phosphonoxy group and salts thereof, an alkyl group, and a glycol structure (also referred to as "functional group 2").
[0044] In another embodiment, the polymer having a constitutional unit represented by formula 2 can contain at least one selected from the group consisting of a carboxy group, an amino group, a hydroxy group, a sulfo group, a phosphonoxy group, and salts thereof, an ester structure, and an amide structure (also referred to as "functional group group 3").
[0045] The above groups and structures contained in each of the functional groups 1 to 3 can be contained in a structural unit other than the structural unit represented by formula 2. In a polymer having a structural unit represented by formula 2, the content of such a structural unit is 0 mol% in one embodiment, and more than 0 mol% in another embodiment, and can be 1 mol% or more or 5 mol% or more (for example, 20 mol% or less, 15 mol% or less, or 10 mol% or less), with the total amount of the structural units constituting this polymer being 100 mol%. Such a structural unit can be represented, for example, by the following formula 100. A polymer having a structural unit represented by formula 2 can contain one or more types of such structural units.
[0046] [ka]
[0047] In formula 100, * represents the position at which the constitutional unit represented by formula 100 is bonded to other partial structures constituting the silicon-containing compound, and R 101 is R in Eq. 21 is synonymous with R 102 is R in Eq. 22 is synonymous with R 103 is R in Eq. 23 The details of these are as described above. In formula 100, R 104 represents at least one selected from the group consisting of functional groups 1 to 3, or represents a substituent containing at least one selected from the group consisting of functional groups 1 to 3. R 104 When R represents at least one selected from the group consisting of functional groups 1 to 3, R 104 can be a carboxy group or a salt thereof. R 104 represents a substituent containing at least one selected from the group consisting of functional groups 1 to 3, R 104 is "-C(=O)OL 100 -Z" where Z represents the group or structure described above, and L 100 represents a single bond or a divalent linking group. 100 The divalent linking group that can be represented by the following formula can be, for example, a linear or branched alkylene group having 1 to 10 carbon atoms, and is preferably a linear alkylene group having 1 to 10 carbon atoms.
[0048] From the viewpoint of further reducing the coefficient of friction after repeated running, the polymer having the structural unit represented by formula 2 preferably contains at least one selected from the above functional group groups 1 to 3, more preferably contains at least one selected from the above functional group groups 2 and 3, even more preferably contains at least one selected from the above functional group group 3, still more preferably contains at least one selected from the group consisting of a carboxy group, an amino group, a sulfo group, a phosphonoxy group, and salts thereof, and even more preferably contains at least one selected from the group consisting of a carboxy group, an amino group, and salts thereof. Furthermore, the present inventors speculate that the above groups and structures included in the above functional group groups 1 to 3 can function as adsorptive functional groups and can contribute, for example, to improving the dispersibility of ferromagnetic powder in the magnetic layer.
[0049] In the present invention and this specification, the average molecular weight (weight average molecular weight and number average molecular weight) refers to a value measured by gel permeation chromatography (GPC) and calculated in terms of standard polystyrene. The weight average molecular weight of the polymer having a constitutional unit represented by formula 2 can be, for example, 1000 or more, 2000 or more, 3000 or more, 4000 or more, 5000 or more, 6000 or more, 7000 or more, or 8000 or more. The weight average molecular weight of the polymer having a constitutional unit represented by formula 2 can be, for example, less than 200,000, 150,000 or less, 100,000 or less, 50,000 or less, or 30,000 or less.
[0050] The polymer containing the constitutional unit represented by formula 2 can be synthesized by a known method. For the synthesis method, for example, known techniques related to the synthesis method of vinyl polymers can be referred to. The compound used as a monomer for synthesizing the polymer containing the constitutional unit represented by formula 2 can be obtained as a commercial product, or can be synthesized by a known method. Specific examples of monomers that can be used to introduce the partial structure represented by formula 1 into the polymer include the following monomers K-1 to K-10.
[0051] [ka]
[0052] Specific examples of polymers containing a structural unit represented by formula 2 include polymers P-1 to P-21 containing the following structural units.
[0053] [ka]
[0054] [ka]
[0055] [ka]
[0056] [ka]
[0057]
change
[0058]
change
[0059]
change
[0060]
change
[0061]
change
[0062]
change
[0063]
change
[0064]
change
[0065]
change
[0066]
change
[0067] [ka]
[0068] [ka]
[0069] [ka]
[0070] [ka]
[0071] [ka]
[0072] [ka]
[0073] [ka]
[0074] However, the present invention is not limited to the above examples.
[0075] (2) Nitrogen-containing polymers In one embodiment, the silicon-containing compound can be a nitrogen-containing polymer. "Nitrogen-containing polymer" refers to a polymer having a plurality of nitrogen-containing structural units. The nitrogen-containing structural unit contained in the nitrogen-containing polymer can be only one type, or can be two or more types.
[0076] The bonding form between the partial structure represented by formula 1 and the nitrogen atom in the nitrogen-containing polymer is not particularly limited. In one embodiment, in the nitrogen-containing polymer, the partial structure represented by formula 1 can be bonded to a carbonyl group (-C(=O)-) directly or through a divalent linking group at the bonding position represented by *, and this carbonyl group can be bonded to a nitrogen atom of the nitrogen-containing polymer. Such a bond can be a covalent bond. In another embodiment, in the nitrogen-containing polymer, the partial structure represented by formula 1 is a carboxylate ion (-C(=O)O) directly or through a divalent linking group at the bonding position represented by *. - ) and such bond can be a covalent bond. And the oxygen anion O of the carboxylate ion - is the nitrogen cation in the nitrogen-containing polymer, N + It is possible to form a salt bridge structure with The divalent linking group is, for example, "-(CH2) n2 The oxygen atom of the ester group (-C(=O)O-) can be bonded to the partial structure of formula 1 at the bonding position represented by *. The above n2 can be, for example, an integer of 1 or more and 10 or less. The nitrogen-containing polymer may contain a plurality of partial structures represented by formula 1 bonded to nitrogen atoms of the nitrogen-containing polymer in different bonding forms or in the same bonding form.
[0077] The nitrogen-containing polymer can be synthesized by reacting a nitrogen-containing polymer (also referred to as "nitrogen-containing raw material polymer") with a silicon-containing compound having a partial structure represented by formula 1 (hereinafter also referred to as "silicon-containing raw material compound"). The reaction can easily proceed by mixing the nitrogen-containing raw material polymer and the silicon-containing raw material compound at room temperature. The "room temperature" described in this specification is a temperature in the range of 0°C to 40°C, preferably a temperature in the range of 10°C to 30°C, and more preferably a temperature in the range of 20 to 25°C. In one embodiment, a magnetic recording medium containing a nitrogen-containing polymer having a partial structure represented by formula 1 in the magnetic layer can be produced by forming a magnetic layer using a nitrogen-containing polymer synthesized by reacting a nitrogen-containing raw material polymer with a silicon-containing raw material compound as a component of a magnetic layer forming composition. In another embodiment, a nitrogen-containing raw material polymer and a silicon-containing raw material compound can be used as components of a magnetic layer forming composition, and these components can be mixed in the preparation process of the magnetic layer forming composition, so that the nitrogen-containing raw material polymer and the silicon-containing raw material compound can be reacted during the preparation process to form a nitrogen-containing polymer having a partial structure represented by formula 1. The above also applies to the case where a nonmagnetic layer containing a nitrogen-containing polymer having the partial structure represented by formula 1 is formed.
[0078] The nitrogen-containing polymer may contain a plurality of polyester chains having the same or different structures. For the polyester chains contained in the nitrogen-containing polymer, the description of the polyester chain described below can be referred to.
[0079] The weight average molecular weight of the nitrogen-containing polymer can be, for example, 3000 or more, 4000 or more, or 5000 or more. The weight average molecular weight of the nitrogen-containing polymer can be, for example, less than 20,000, 15,000 or less, or 10,000 or less.
[0080] In one embodiment, the nitrogen-containing polymer can be a polyalkyleneimine-based polymer. In the present invention and this specification, a "polyalkyleneimine-based polymer" is a polymer containing one or more polyalkyleneimine chains. A polyalkyleneimine chain is a polymer structure containing two or more identical or different alkyleneimine chains. The polyalkyleneimine chain is described further below. In one embodiment, it is believed that the polyalkyleneimine chain can function as an adsorption site to the ferromagnetic powder contained in the magnetic layer.
[0081] In the following, a polyalkyleneimine-based polymer that can be used as a nitrogen-containing raw material polymer when the nitrogen-containing polymer is a polyalkyleneimine-based polymer will be described. The following description of the polyalkyleneimine-based polymer also applies to the case where the nitrogen-containing polymer is a polyalkyleneimine-based polymer, unless otherwise specified.
[0082] (Nitrogen-containing raw polymer) Polyalkyleneimine Chain When the nitrogen-containing polymer is a polyalkyleneimine-based polymer, in one embodiment, the nitrogen-containing raw polymer that can be used to obtain such a nitrogen-containing polymer can be a polyalkyleneimine-based polymer having a polyester chain.In another embodiment, a polyalkyleneimine-based polymer that does not have a polyester chain can be used as the nitrogen-containing raw polymer.In another embodiment, a polyalkyleneimine-based polymer that does not have a polyester chain can be used as the nitrogen-containing raw polymer, and this polymer, polyester, and silicon-containing raw compound described later can be reacted simultaneously or sequentially to obtain a polyalkyleneimine-based polymer having a polyester chain and a partial structure represented by formula 1.
[0083] When the nitrogen-containing raw polymer is a polyalkyleneimine polymer, examples of the alkyleneimine chain contained in the polyalkyleneimine polymer include an alkyleneimine chain represented by the following formula A and an alkyleneimine chain represented by the following formula B. Among the alkyleneimine chains represented by the following formulas, the alkyleneimine chain represented by formula A can include a bonding site with a polyester chain described below. In addition, the alkyleneimine chain represented by formula B can bond to a polyester chain by forming a salt bridge structure. In addition, the polyalkyleneimine chain may be composed of only a straight chain structure or may have a branched tertiary amine structure. Examples of those containing a branched structure include * in the following formula A. 1 and * in the following formula B 2 and the like, which is bonded to an adjacent alkyleneimine chain in the following formula:
[0084] [ka]
[0085] In formula A, R 1 and R 2 each independently represents a hydrogen atom or an alkyl group, a1 represents an integer of 2 or more, * 1 represents a bonding position to another adjacent polymer chain (for example, an adjacent alkyleneimine chain, a polyester chain described below, etc.), or to a hydrogen atom or a substituent.
[0086] [ka]
[0087] In formula B, R 3 and R 4 each independently represents a hydrogen atom or an alkyl group, and a2 represents an integer of 2 or more. In the alkyleneimine chain represented by formula B, the anionic group of another polymer chain and N in formula B + and can form a salt bridge structure.
[0088] * in formula A and formula B, and * in formula B 2 each independently represents a position at which the group is bonded to an adjacent alkyleneimine chain, or a hydrogen atom or a substituent.
[0089] The above formulae A and B will now be described in more detail.
[0090] R in formula A 1 and R 2 and R in formula B 3 and R 4 Each of R independently represents a hydrogen atom or an alkyl group. Examples of the alkyl group include an alkyl group having 1 to 6 carbon atoms, preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group or an ethyl group, and further preferably a methyl group. 1 and R 2 The combination of R in formula B includes a form in which one is a hydrogen atom and the other is an alkyl group, a form in which both are hydrogen atoms, and a form in which both are alkyl groups (the same or different alkyl groups), and preferably a form in which both are hydrogen atoms. 3 and R 4 The same applies to.
[0091] The structure with the smallest number of carbon atoms constituting the ring as an alkyleneimine is ethyleneimine, and the number of carbon atoms in the main chain of the alkyleneimine chain (ethyleneimine chain) obtained by ring-opening of ethyleneimine is 2. Therefore, the lower limit of a1 in formula A and a2 in formula B is 2. That is, a1 in formula A and a2 in formula B are each independently an integer of 2 or more. a1 in formula A and a2 in formula B can each independently be, for example, 10 or less, preferably 6 or less, more preferably 4 or less, even more preferably 2 or 3, and even more preferably 2.
[0092] The details of the bonds between the alkyleneimine chain represented by formula A and the alkyleneimine chain represented by formula B and the polyester chain, and the formation of the salt bridge structure will be described later.
[0093] Each of the alkyleneimine chains is bonded to an adjacent alkyleneimine chain, or a hydrogen atom or a substituent at the position represented by * in each formula. Examples of the substituent include monovalent substituents such as alkyl groups (e.g., alkyl groups having 1 to 6 carbon atoms), but are not limited thereto. In addition, other polymer chains (e.g., polyester chains described below) may be bonded as the substituent.
[0094] The number average molecular weight of the polyalkyleneimine chain contained in the polyalkyleneimine-based polymer is preferably 300 or more, more preferably 500 or more. The number average molecular weight of the polyalkyleneimine chain is preferably 3000 or less, more preferably 2000 or less. The number average molecular weight of the polyalkyleneimine used to synthesize the polyalkyleneimine-based polymer can be adopted as the number average molecular weight of the polyalkyleneimine chain contained in the polyalkyleneimine-based polymer.
[0095] Polyester Chain The polyalkyleneimine-based polymer that can be used as the nitrogen-containing raw material polymer can contain a polyester chain in addition to the polyalkyleneimine chain described above. When the silicon-containing compound is a polyalkyleneimine-based polymer, the polyalkyleneimine-based polymer can contain a polyalkyleneimine chain and a polyester chain. In the present invention and this specification, the term "polyester chain" refers to a polymer chain having a plurality of ester groups. In one embodiment, the polyester chain is an alkyleneimine chain represented by formula A and a * in formula A. 1 In another embodiment, the alkyleneimine chain and the polyester chain represented by formula B can be bonded to the nitrogen atom N contained in formula A via a carbonyl group -(C=O)- to form -N-(C=O)-. In another embodiment, the alkyleneimine chain and the polyester chain represented by formula B can be bonded to the nitrogen cation N + The polyester chain has an anionic group, and the polyester chain has an anionic group, which can form a salt bridge structure.- and N in formula B + Examples of the material include, but are not limited to, those formed by:
[0096] An example of a polyester chain formed by bonding an alkyleneimine chain represented by formula A and a nitrogen atom N contained in formula A via a carbonyl group -(C=O)- is a polyester chain represented by the following formula 11. The polyester chain represented by the following formula 11 is: 1 At the bonding position represented by the formula:, a nitrogen atom contained in the alkyleneimine chain and a carbonyl group -(C=O)- contained in the polyester chain form -N-(C=O)-, thereby bonding to the alkyleneimine chain represented by the formula A.
[0097] [ka]
[0098] In addition, the alkyleneimine chain represented by formula B and N in formula B + An example of a polyester chain in which an anionic group contained in the polyester chain forms a salt bridge structure and bonds with the polyester chain is a polyester chain represented by the following formula 12. The polyester chain represented by the following formula 12 is an oxygen anion O - Thus, the nitrogen cation N in formula B + It is possible to form a salt bridge structure with
[0099] [ka]
[0100] L in Equation 11 1 and L in Eq. 2 each independently represents a divalent linking group. The divalent linking group is preferably an alkylene group having 3 to 30 carbon atoms. When the alkylene group has a substituent, the number of carbon atoms of the alkylene group refers to the number of carbon atoms in the portion excluding the substituent (i.e., the main chain portion), as described above.
[0101] b11 in formula 11 and b21 in formula 2 each independently represent an integer of 2 or more, for example, an integer of 200 or less.
[0102] b12 in formula 11 and b22 in formula 2 each independently represent 0 or 1.
[0103] X in formula 11 1 and X in Eq. 2 each independently represents a hydrogen atom or a monovalent substituent. Examples of the monovalent substituent include a monovalent substituent selected from the group consisting of an alkyl group, an alkoxy group, a polyalkyleneoxyalkyl group, and an aryl group.
[0104] The alkyl group may have a substituent or may be unsubstituted. As the alkyl group having a substituent, an alkyl group substituted with a hydroxy group (hydroxyalkyl group) is preferable. As the alkyl group, an alkyl group having 1 to 30 carbon atoms is more preferable, and an alkyl group having 1 to 10 carbon atoms is even more preferable. The alkyl group may be linear, branched, or cyclic.
[0105] For specific examples of substituted or unsubstituted alkyl groups, see paragraph 0052 of JP2015-28830A. For specific examples of alkoxy groups, see paragraph 0053 of JP2015-28830A.
[0106] Polyalkyleneoxyalkyl groups are R 70 (OR 71 ) n1 (O) m1 R is a monovalent substituent represented by the formula: 70 represents an alkyl group, R 71 represents an alkylene group, n1 represents an integer of 2 or more, and m1 represents 0 or 1. R 70 For the alkyl group represented by X 1 , X 2 The alkyl group represented by R 71For details of the alkylene group represented by X 1 , X 2 The above description of the alkyl group represented by the following formula (1) can be applied to these alkylene groups by removing one hydrogen atom from them (for example, a methyl group can be replaced with a methylene group). n1 is an integer of 2 or more, for example, an integer of 10 or less, preferably an integer of 5 or less.
[0107] The aryl group may have a substituent or may be a condensed ring, and is more preferably an aryl group having 6 to 24 carbon atoms, such as a phenyl group, a 4-methylphenyl group, a 4-phenylbenzoic acid group, a 3-cyanophenyl group, a 2-chlorophenyl group, and a 2-naphthyl group.
[0108] The polyester chain represented by the formula 11 and the polyester chain represented by the formula 12 described above can each be a structure derived from a polyester obtained by a known polyester synthesis method. For example, the polyester synthesis method can be ring-opening polymerization of lactone. For example, various lactones described in paragraph 0056 of JP-A-2015-28830 can be exemplified as lactones. As lactones, ε-caprolactone, lactide, or δ-valerolactone are preferred from the viewpoint of reactivity and / or availability. However, the lactones are not limited to these, and any lactone may be used as long as it is capable of obtaining a polyester by ring-opening polymerization.
[0109] For nucleophilic reagents for ring-opening polymerization of lactones, reference can be made to paragraph 0057 of JP2015-28830A.
[0110] However, the polyester chain is not limited to a structure derived from a polyester obtained by ring-opening polymerization of lactone, and may also be a structure derived from a polyester obtained by a known polyester synthesis method, for example, polycondensation of a polyvalent carboxylic acid and a polyhydric alcohol, or polycondensation of a hydroxycarboxylic acid.
[0111] In one embodiment, the weight average molecular weight of the polyester chain is preferably 200 or more, more preferably 400 or more, and even more preferably 500 or more. In one embodiment, the number average molecular weight of the polyester chain is preferably 100,000 or less, and more preferably 50,000 or less.
[0112] Weight average molecular weight of nitrogen-containing raw polymer The average molecular weight of the polyalkyleneimine polymer that can be used as the nitrogen-containing raw polymer can be, for example, 1000 or more, and can be, for example, 80000 or less, as a weight average molecular weight. The weight average molecular weight of the polyalkyleneimine polymer that can be used as the nitrogen-containing raw polymer is preferably 1500 or more, more preferably 2000 or more, and even more preferably 3000 or more. In one embodiment, the weight average molecular weight of the polyalkyleneimine polymer that can be used as the nitrogen-containing raw polymer is preferably 60000 or less, more preferably 40000 or less, even more preferably 35000 or less, even more preferably 34000 or less, even more preferably 30000 or less, even more preferably 20000 or less, and even more preferably 10000 or less.
[0113] Synthesis method The synthesis method of the polyalkyleneimine polymer used as the nitrogen-containing raw polymer is not particularly limited. For one embodiment of the synthesis method, refer to paragraphs 0061 to 0069 of JP2015-28830A and the section of Examples of the same publication.
[0114] (Silicon-containing raw material compounds) Silicon-containing raw material compounds can be obtained as commercial products, and can also be synthesized by known methods. An example of a silicon-containing raw material compound is a carboxyl group-containing compound having a partial structure represented by formula 1. With such a compound, the carboxyl group of this compound bonds with the nitrogen atom of the nitrogen-containing raw material polymer and / or forms a salt bridge structure, thereby introducing the partial structure represented by formula 1 into the nitrogen-containing polymer in the above-described bond form. Specific examples of carboxyl group-containing compounds having a partial structure represented by formula 1 include the following compounds S-1 and S-2. However, the present invention is not limited to these examples.
[0115] [ka]
[0116] For example, the magnetic layer or the composition for forming the magnetic layer may contain 0.1 parts by mass or more of the silicon-containing compound per 100 parts by mass of ferromagnetic powder, and preferably 0.5 parts by mass or more. The content of the silicon-containing compound in the magnetic layer or the composition for forming the magnetic layer may be, for example, 50.0 parts by mass or less, 40.0 parts by mass or less, 30.0 parts by mass or less, 20.0 parts by mass or less, 15.0 parts by mass or less, or 10.0 parts by mass or less per 100 parts by mass of ferromagnetic powder. The silicon-containing compound contained in the magnetic layer or the composition for forming the magnetic layer may be only one type or two or more types. When two or more types are contained, the above content is the total content of the two or more types. Furthermore, when a nitrogen-containing raw material polymer and a silicon-containing raw material compound are used as components of the magnetic layer forming composition, the contents of the nitrogen-containing raw material polymer and the silicon-containing raw material compound in the magnetic layer forming composition are as follows. The content of the nitrogen-containing raw polymer in the magnetic layer forming composition is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, per 100 parts by mass of the ferromagnetic powder. The content of the nitrogen-containing raw polymer in the magnetic layer forming composition can be, for example, 20.0 parts by mass or less, 15.0 parts by mass or less, or 10.0 parts by mass or less, per 100 parts by mass of the ferromagnetic powder. The content of the silicon-containing raw material compound in the magnetic layer forming composition is preferably 1.0 mass parts or more, more preferably 3.0 mass parts or more, and even more preferably 5.0 mass parts or more per 100 mass parts of ferromagnetic powder. The content of the silicon-containing raw material compound in the magnetic layer forming composition can be, for example, 20.0 mass parts or less, 15.0 mass parts or less, or 10.0 mass parts or less per 100 mass parts of ferromagnetic powder. For the nonmagnetic layer and the composition for forming the nonmagnetic layer, the above description can be applied by replacing the ferromagnetic powder with a nonmagnetic powder. Regarding the mixing ratio of the nitrogen-containing raw material polymer and the silicon-containing raw material compound, the total amount (by mass) of the nitrogen-containing raw material polymer and the silicon-containing raw material compound is 100 mass%, and the ratio of the silicon-containing raw material compound can be 10 mass% or more, 15 mass% or more, 20 mass% or more, 25 mass% or more, or 30 mass% or more, and can be 90 mass% or less, 80 mass% or less, 70 mass% or less, 60 mass% or less, or 50 mass% or less.
[0117] The magnetic recording medium may or may not contain a nitrogen-containing polymer not having the partial structure represented by formula 1 (hereinafter also referred to as "other nitrogen-containing polymer") together with the silicon-containing compound in the magnetic layer side portion on the non-magnetic support. In one embodiment, the other nitrogen-containing polymer may be the polyalkyleneimine-based polymer described above as an example of the nitrogen-containing raw material polymer. The polyalkyleneimine-based polymer described above can function as a dispersant for improving the dispersibility of ferromagnetic powder. The nitrogen-containing polymer, which is one embodiment of the silicon-containing compound, can also function as a dispersant for improving the dispersibility of ferromagnetic powder. When another nitrogen-containing polymer is included, the content of the other nitrogen-containing polymer in the magnetic layer or magnetic layer-forming composition can be, for example, 0.1 to 20.0 parts by mass, or 1.0 to 15.0 parts by mass, per 100 parts by mass of the ferromagnetic powder. For the nonmagnetic layer and the nonmagnetic layer-forming composition, the above description can be applied by replacing the ferromagnetic powder with the nonmagnetic powder.
[0118] The magnetic layer of the magnetic recording medium will now be described in more detail. <Magnetic layer> (Ferromagnetic powder) The magnetic layer contains ferromagnetic powder. As the ferromagnetic powder contained in the magnetic layer, one or more of known ferromagnetic powders used in the magnetic layers of various magnetic recording media can be used in combination. It is preferable to use ferromagnetic powders with a small average particle size from the viewpoint of improving recording density. From this viewpoint, the average particle size of the ferromagnetic powder is preferably 50 nm or less, more preferably 45 nm or less, even more preferably 40 nm or less, even more preferably 35 nm or less, even more preferably 30 nm or less, even more preferably 25 nm or less, and even more preferably 20 nm or less. On the other hand, from the viewpoint of magnetization stability, the average particle size of the ferromagnetic powder is preferably 5 nm or more, more preferably 8 nm or more, even more preferably 10 nm or more, even more preferably 15 nm or more, and even more preferably 20 nm or more.
[0119] Hexagonal Ferrite Powder A preferred specific example of the ferromagnetic powder is hexagonal ferrite powder. For details of the hexagonal ferrite powder, see, for example, JP2011-225417A, paragraphs 0012-0030, JP2011-216149A, paragraphs 0134-0136, JP2012-204726A, paragraphs 0013-0030, and JP2015-127985A, paragraphs 0029-0084.
[0120] In the present invention and this specification, the term "hexagonal ferrite powder" refers to a ferromagnetic powder in which the crystal structure of hexagonal ferrite is detected as the main phase by X-ray diffraction analysis. The main phase refers to the structure to which the diffraction peak with the highest intensity is assigned in the X-ray diffraction spectrum obtained by X-ray diffraction analysis. For example, when the diffraction peak with the highest intensity in the X-ray diffraction spectrum obtained by X-ray diffraction analysis is assigned to the crystal structure of hexagonal ferrite, it is determined that the crystal structure of hexagonal ferrite is detected as the main phase. When only a single structure is detected by X-ray diffraction analysis, the detected structure is regarded as the main phase. The crystal structure of hexagonal ferrite contains at least an iron atom, a divalent metal atom, and an oxygen atom as constituent atoms. The divalent metal atom is a metal atom that can become a divalent cation as an ion, and examples of the divalent metal atom include an alkaline earth metal atom such as a strontium atom, a barium atom, and a calcium atom, and a lead atom. In the present invention and this specification, the hexagonal strontium ferrite powder refers to a powder in which the main divalent metal atom contained therein is a strontium atom, and the hexagonal barium ferrite powder refers to a powder in which the main divalent metal atom contained therein is a barium atom. The main divalent metal atom refers to the divalent metal atom that is the most abundant of the divalent metal atoms contained in the powder on an atomic % basis. However, the above divalent metal atoms do not include rare earth atoms. In the present invention and this specification, the "rare earth atom" is selected from the group consisting of scandium atoms (Sc), yttrium atoms (Y), and lanthanoid atoms. The lanthanide atom is selected from the group consisting of a lanthanum atom (La), a cerium atom (Ce), a praseodymium atom (Pr), a neodymium atom (Nd), a promethium atom (Pm), a samarium atom (Sm), a europium atom (Eu), a gadolinium atom (Gd), a terbium atom (Tb), a dysprosium atom (Dy), a holmium atom (Ho), an erbium atom (Er), a thulium atom (Tm), a ytterbium atom (Yb), and a lutetium atom (Lu).
[0121] Hereinafter, hexagonal strontium ferrite powder, which is one form of hexagonal ferrite powder, will be described in more detail.
[0122] The activation volume of the hexagonal strontium ferrite powder is preferably 800 to 1500 nm 3 The finely divided hexagonal strontium ferrite powder exhibiting an activation volume in the above range is suitable for producing a magnetic recording medium exhibiting excellent electromagnetic conversion characteristics. The activation volume of the hexagonal strontium ferrite powder is preferably 800 nm 3 For example, 850 nm or more. 3 From the viewpoint of further improving the electromagnetic conversion characteristics, the activation volume of the hexagonal strontium ferrite powder can be 1400 nm or more. 3 More preferably, it is 1300 nm or less. 3 More preferably, it is 1200 nm or less. 3 More preferably, it is equal to or less than 1100 nm. 3 It is even more preferred that:
[0123] "Activation volume" is a unit of magnetization reversal and is an index showing the magnetic size of a particle. The activation volume and the anisotropy constant Ku described in the present invention and this specification are values obtained by measuring the coercive force Hc measurement section at magnetic field sweep speeds of 3 minutes and 30 minutes (measurement temperature: 23°C ± 1°C) using a vibrating sample magnetometer, and calculating from the following relationship between Hc and activation volume V. The unit of the anisotropy constant Ku is 1 erg / cc = 1.0 x 10 -1 J / m 3 It is. Hc=2Ku / Ms{1-[(kT / KuV)ln(At / 0.693)] 1 / 2} [In the above formula, Ku: anisotropy constant (unit: J / m 3 ), Ms: saturation magnetization (unit: kA / m), k: Boltzmann constant, T: absolute temperature (unit: K), V: activation volume (unit: cm 3 ), A: spin precession frequency (unit: s -1 ), t: magnetic field reversal time (unit: s)]
[0124] The anisotropy constant Ku can be used as an index of reduction in thermal fluctuation, in other words, improvement in thermal stability. The hexagonal strontium ferrite powder is preferably 1.8×10 5 J / m 3 More preferably, the Ku is 2.0×10 or more. 5 J / m 3 The Ku of the hexagonal strontium ferrite powder can be, for example, 2.5×10 5 J / m 3 However, since a higher Ku value means higher thermal stability and is therefore preferred, the Ku value is not limited to the above-mentioned values.
[0125] The hexagonal strontium ferrite powder may or may not contain rare earth atoms. When the hexagonal strontium ferrite powder contains rare earth atoms, it is preferable that the rare earth atoms are contained at a content (bulk content) of 0.5 to 5.0 atomic % relative to 100 atomic % of iron atoms. In one embodiment, the hexagonal strontium ferrite powder containing rare earth atoms can have uneven distribution of rare earth atoms in the surface layer portion. In the present invention and this specification, the term "surface distribution of rare earth atoms" refers to the rare earth atom content relative to 100 atomic % of iron atoms in a solution obtained by partially dissolving a hexagonal strontium ferrite powder in an acid (hereinafter referred to as "surface content of rare earth atoms" or simply "surface content" for rare earth atoms), which is greater than the rare earth atom content relative to 100 atomic % of iron atoms in a solution obtained by completely dissolving a hexagonal strontium ferrite powder in an acid (hereinafter referred to as "bulk content of rare earth atoms" or simply "bulk content" for rare earth atoms), Rare earth atom surface content / rare earth atom bulk content>1.0 The rare earth atom content of the hexagonal strontium ferrite powder described later is synonymous with the rare earth atom bulk content. In contrast, partial dissolution using an acid dissolves the surface layer of the particles constituting the hexagonal strontium ferrite powder, so the rare earth atom content in the solution obtained by partial dissolution is the rare earth atom content in the surface layer of the particles constituting the hexagonal strontium ferrite powder. The rare earth atom surface layer content satisfying the ratio of "rare earth atom surface layer content / rare earth atom bulk content>1.0" means that the rare earth atoms are unevenly distributed (i.e., more present in the surface layer) in the particles constituting the hexagonal strontium ferrite powder. In the present invention and this specification, the surface layer refers to a portion of the region extending from the surface of the particles constituting the hexagonal strontium ferrite powder toward the inside.
[0126] When the hexagonal strontium ferrite powder contains rare earth atoms, the rare earth atom content (bulk content) is preferably in the range of 0.5 to 5.0 atomic % relative to 100 atomic % of iron atoms. It is considered that the rare earth atoms contained in the bulk content in the above range and the rare earth atoms unevenly distributed in the surface layer of the particles constituting the hexagonal strontium ferrite powder contribute to suppressing the decrease in the reproduction output during repeated reproduction. This is presumed to be because the hexagonal strontium ferrite powder contains rare earth atoms in the bulk content in the above range and the rare earth atoms unevenly distributed in the surface layer of the particles constituting the hexagonal strontium ferrite powder can increase the anisotropy constant Ku. The higher the value of the anisotropy constant Ku, the more the occurrence of a phenomenon called thermal fluctuation can be suppressed (in other words, the thermal stability can be improved). By suppressing the occurrence of thermal fluctuation, the decrease in the reproduction output during repeated reproduction can be suppressed. It is speculated that the uneven distribution of rare earth atoms in the surface layer of hexagonal strontium ferrite powder particles contributes to stabilizing the spin of the iron (Fe) sites in the crystal lattice of the surface layer, thereby increasing the anisotropy constant Ku. In addition, it is presumed that using the hexagonal strontium ferrite powder having rare earth atom uneven distribution on the surface as the ferromagnetic powder of the magnetic layer also contributes to suppressing the wear of the magnetic layer surface due to sliding with the magnetic head. That is, it is presumed that the hexagonal strontium ferrite powder having rare earth atom uneven distribution on the surface can also contribute to improving the running durability of the magnetic recording medium. This is presumed to be because the uneven distribution of rare earth atoms on the surface of the particles constituting the hexagonal strontium ferrite powder contributes to improving the interaction between the particle surface and the organic substance (e.g., binder and / or additive) contained in the magnetic layer, and as a result, the strength of the magnetic layer is improved. From the viewpoint of further suppressing the decrease in regeneration output during repeated regeneration and / or further improving running durability, the rare earth atom content (bulk content) is more preferably in the range of 0.5 to 4.5 atomic %, even more preferably in the range of 1.0 to 4.5 atomic %, and even more preferably in the range of 1.5 to 4.5 atomic %.
[0127] The bulk content is the content obtained by completely dissolving the hexagonal strontium ferrite powder. In the present invention and this specification, unless otherwise specified, the content of an atom refers to the bulk content obtained by completely dissolving the hexagonal strontium ferrite powder. The hexagonal strontium ferrite powder containing rare earth atoms may contain only one rare earth atom as a rare earth atom, or may contain two or more rare earth atoms. The bulk content when containing two or more rare earth atoms is obtained for the total of two or more rare earth atoms. This point is the same for other components in the present invention and this specification. That is, unless otherwise specified, a certain component may be used only one type, or two or more types may be used. When two or more types are used, the content or content refers to the total of two or more types.
[0128] When the hexagonal strontium ferrite powder contains rare earth atoms, the rare earth atoms contained therein may be any one or more of rare earth atoms. From the viewpoint of further suppressing the decrease in the reproduction output during repeated reproduction, preferred rare earth atoms include neodymium atoms, samarium atoms, yttrium atoms and dysprosium atoms, more preferred are neodymium atoms, samarium atoms and yttrium atoms, and even more preferred are neodymium atoms.
[0129] In the hexagonal strontium ferrite powder having rare earth atom uneven distribution in the surface layer, the rare earth atoms may be unevenly distributed in the surface layer of the particles constituting the hexagonal strontium ferrite powder, and the degree of uneven distribution is not limited. For example, for the hexagonal strontium ferrite powder having rare earth atom uneven distribution in the surface layer, the ratio of the surface content of rare earth atoms obtained by partial dissolution under the dissolution conditions described below to the bulk content of rare earth atoms obtained by complete dissolution under the dissolution conditions described below, "surface content / bulk content", is more than 1.0 and can be 1.5 or more. The "surface content / bulk content" being greater than 1.0 means that the rare earth atoms are unevenly distributed in the surface layer (i.e., more than in the interior) in the particles constituting the hexagonal strontium ferrite powder. In addition, the ratio of the surface layer content of rare earth atoms obtained by partial dissolution under the dissolution conditions described later to the bulk content of rare earth atoms obtained by total dissolution under the dissolution conditions described later, "surface layer content / bulk content", can be, for example, 10.0 or less, 9.0 or less, 8.0 or less, 7.0 or less, 6.0 or less, 5.0 or less, or 4.0 or less. However, in a hexagonal strontium ferrite powder having rare earth atom surface layer uneven distribution, it is sufficient that the rare earth atoms are unevenly distributed in the surface layer of the particles constituting the hexagonal strontium ferrite powder, and the above "surface layer content / bulk content" is not limited to the upper or lower limit exemplified.
[0130] The partial and total dissolution of hexagonal strontium ferrite powder will be described below. For hexagonal strontium ferrite powder present as powder, the sample powders to be partially and completely dissolved are taken from the same lot of powder. On the other hand, for hexagonal strontium ferrite powder contained in the magnetic layer of a magnetic recording medium, a part of the hexagonal strontium ferrite powder taken out of the magnetic layer is subjected to partial dissolution, and the other part is subjected to total dissolution. The hexagonal strontium ferrite powder can be taken out of the magnetic layer by, for example, the method described in paragraph 0032 of JP 2015-91747 A. The above-mentioned partial dissolution means that the hexagonal strontium ferrite powder is dissolved to such an extent that the remaining powder can be visually confirmed in the liquid at the end of dissolution. For example, the partial dissolution can dissolve a region of 10 to 20 mass% of the particles constituting the hexagonal strontium ferrite powder, with the whole particles being 100 mass%. On the other hand, the above-mentioned complete dissolution means that the hexagonal strontium ferrite powder is dissolved to such an extent that the remaining powder cannot be visually confirmed in the liquid at the end of dissolution. The partial dissolution and the surface layer content are measured, for example, by the following method. Note that the dissolution conditions such as the amount of sample powder are merely examples, and any dissolution conditions that allow partial or complete dissolution can be used. A container (e.g., a beaker) containing 12 mg of sample powder and 10 mL of 1 mol / L hydrochloric acid is placed on a hot plate set at 70°C for 1 hour. The resulting solution is filtered through a 0.1 μm membrane filter. Elemental analysis of the filtrate thus obtained is performed using an inductively coupled plasma (ICP) analyzer. In this way, the surface layer content of rare earth atoms relative to 100 atomic % of iron atoms can be determined. When multiple types of rare earth atoms are detected by elemental analysis, the total content of all rare earth atoms is taken as the surface layer content. This is also true for the measurement of bulk content. On the other hand, the total dissolved and bulk contents are measured, for example, by the following method. A container (e.g., a beaker) containing 12 mg of sample powder and 10 mL of 4 mol / L hydrochloric acid is placed on a hot plate set at 80° C. for 3 hours. After that, the bulk content relative to 100 atomic % of iron atoms can be calculated by carrying out the same procedure as the partial dissolution and surface layer content measurement described above.
[0131] From the viewpoint of increasing the reproduction output when reproducing data recorded on a magnetic recording medium, it is desirable for the mass magnetization σs of the ferromagnetic powder contained in the magnetic recording medium to be high. In this regard, hexagonal strontium ferrite powder containing rare earth atoms but not having uneven distribution of rare earth atoms in the surface layer has a tendency to have a significantly lower σs than hexagonal strontium ferrite powder not containing rare earth atoms. In contrast, hexagonal strontium ferrite powder having uneven distribution of rare earth atoms in the surface layer is considered to be preferable in terms of suppressing such a large decrease in σs. In one embodiment, the σs of the hexagonal strontium ferrite powder is 45 A·m 2 / kg or more, and 47A·m 2 / kg or more. On the other hand, from the viewpoint of noise reduction, σs is 80A·m 2 / kg or less, and 60A·m 2 / kg or less is more preferable. σs can be measured using a known measuring device capable of measuring magnetic properties, such as a vibrating sample magnetometer. In the present invention and this specification, unless otherwise specified, the mass magnetization σs is a value measured at a magnetic field strength of 1194 kA / m (15 kOe).
[0132] Regarding the content (bulk content) of the constituent atoms of the hexagonal strontium ferrite powder, the strontium atom content can be, for example, in the range of 2.0 to 15.0 atomic % relative to 100 atomic % of iron atoms. In one embodiment, the divalent metal atoms contained in the hexagonal strontium ferrite powder can be only strontium atoms. In another embodiment, the hexagonal strontium ferrite powder can also contain one or more other divalent metal atoms in addition to strontium atoms. For example, it can contain barium atoms and / or calcium atoms. When divalent metal atoms other than strontium atoms are contained, the barium atom content and calcium atom content in the hexagonal strontium ferrite powder can each be, for example, in the range of 0.05 to 5.0 atomic % relative to 100 atomic % of iron atoms.
[0133] Known crystal structures of hexagonal ferrite include magnetoplumbite type (also called "M type"), W type, Y type, and Z type. The hexagonal strontium ferrite powder may have any of the crystal structures. The crystal structure can be confirmed by X-ray diffraction analysis. The hexagonal strontium ferrite powder may be one in which a single crystal structure or two or more types of crystal structures are detected by X-ray diffraction analysis. For example, in one embodiment, the hexagonal strontium ferrite powder may be one in which only the M-type crystal structure is detected by X-ray diffraction analysis. For example, M-type hexagonal ferrite is AFe 12 O 19Here, A represents a divalent metal atom, and when the hexagonal strontium ferrite powder is of the M type, A is only a strontium atom (Sr), or when A contains a plurality of divalent metal atoms, the strontium atom (Sr) accounts for the largest proportion on an atomic % basis as described above. The divalent metal atom content of the hexagonal strontium ferrite powder is usually determined by the type of crystal structure of the hexagonal ferrite, and is not particularly limited. The same applies to the iron atom content and the oxygen atom content. The hexagonal strontium ferrite powder contains at least an iron atom, a strontium atom, and an oxygen atom, and may further contain a rare earth atom. Furthermore, the hexagonal strontium ferrite powder may or may not contain atoms other than these atoms. As an example, the hexagonal strontium ferrite powder may contain an aluminum atom (Al). The content of aluminum atoms can be, for example, 0.5 to 10.0 atomic % relative to 100 atomic % of iron atoms. From the viewpoint of further suppressing the decrease in the reproduction output during repeated reproduction, the hexagonal strontium ferrite powder contains iron atoms, strontium atoms, oxygen atoms, and rare earth atoms, and the content of atoms other than these atoms is preferably 10.0 atomic % or less, more preferably in the range of 0 to 5.0 atomic %, relative to 100 atomic % of iron atoms, and may be 0 atomic %. That is, in one embodiment, the hexagonal strontium ferrite powder may not contain atoms other than iron atoms, strontium atoms, oxygen atoms, and rare earth atoms. The content expressed in atomic % above is obtained by converting the content (unit: mass %) of each atom obtained by completely dissolving the hexagonal strontium ferrite powder into a value expressed in atomic % using the atomic weight of each atom. In addition, in the present invention and this specification, "not containing" a certain atom means that the content measured by an ICP analyzer after completely dissolving is 0 mass %. The detection limit of an ICP analyzer is usually 0.01 ppm (parts per million) or less on a mass basis. The above term "free" is used to mean that the content is below the detection limit of the ICP analyzer.In one form, the hexagonal strontium ferrite powder can be one that does not contain bismuth atoms (Bi).
[0134] metal powder A specific preferred example of the ferromagnetic powder is a ferromagnetic metal powder. For details of the ferromagnetic metal powder, reference can be made to, for example, paragraphs 0137 to 0141 of JP 2011-216149 A and paragraphs 0009 to 0023 of JP 2005-251351 A.
[0135] ε-iron oxide powder A preferred specific example of the ferromagnetic powder is ε-iron oxide powder. In the present invention and this specification, the term "ε-iron oxide powder" refers to a ferromagnetic powder in which the ε-iron oxide crystal structure is detected as the main phase by X-ray diffraction analysis. For example, when the highest intensity diffraction peak in the X-ray diffraction spectrum obtained by X-ray diffraction analysis is assigned to the ε-iron oxide crystal structure, it is determined that the ε-iron oxide crystal structure is detected as the main phase. Known methods for producing ε-iron oxide powder include a method of producing it from goethite and a reverse micelle method. All of the above production methods are publicly known. In addition, for a method for producing ε-iron oxide powder in which a part of Fe is replaced by a substitution atom such as Ga, Co, Ti, Al, or Rh, reference can be made to, for example, J. Jpn. Soc. Powder Metallurgy Vol. 61 Supplement, No. S1, pp. S280-S284, J. Mater. Chem. C, 2013, 1, pp.5200-5206, etc. However, the method for producing the ε-iron oxide powder that can be used as the ferromagnetic powder in the magnetic layer of the magnetic recording medium is not limited to the method given here.
[0136] The activation volume of the ε-iron oxide powder is preferably 300 to 1500 nm 3 The finely divided ε-iron oxide powder exhibiting an activation volume in the above range is suitable for producing a magnetic recording medium exhibiting excellent electromagnetic conversion characteristics. The activation volume of the ε-iron oxide powder is preferably 300 nm 3For example, 500 nm or more. 3 From the viewpoint of further improving the electromagnetic conversion characteristics, the activation volume of the ε-iron oxide powder can be 1400 nm or more. 3 More preferably, it is 1300 nm or less. 3 More preferably, it is 1200 nm or less. 3 More preferably, it is equal to or less than 1100 nm. 3 It is even more preferred that:
[0137] The anisotropy constant Ku can be used as an index of the reduction in thermal fluctuation, in other words, the improvement in thermal stability. The ε-iron oxide powder is preferably 3.0×10 4 J / m 3 More preferably, the Ku is 8.0×10 or more. 4 J / m 3 The Ku of the ε-iron oxide powder can be, for example, 3.0×10 5 J / m 3 However, since a higher Ku value means higher thermal stability and is preferable, the Ku value is not limited to the above-mentioned values.
[0138] From the viewpoint of increasing the reproduction output when reproducing data recorded on the magnetic recording medium, it is desirable that the mass magnetization σs of the ferromagnetic powder contained in the magnetic recording medium is high. In this regard, in one embodiment, the σs of the ε-iron oxide powder is 8 A m 2 / kg or more, and 12 A m 2 On the other hand, the σs of ε-iron oxide powder is 40 A m 2 / kg or less, and 35A·m 2 It is more preferable that the amount is not more than 1 / kg.
[0139] In the present invention and this specification, unless otherwise specified, the average particle size of various powders such as ferromagnetic powders is a value measured by the following method using a transmission electron microscope. The powder is photographed at a magnification of 100,000 times using a transmission electron microscope, and a photograph of the particles that make up the powder is obtained by printing it on photographic paper or displaying it on a display so that the total magnification is 500,000 times. From the obtained particle photograph, the target particle is selected, and the particle outline is traced with a digitizer to measure the particle (primary particle) size. Primary particles are independent particles that are not aggregated. The above measurements are carried out for 500 randomly selected particles. The arithmetic mean of the particle sizes of the 500 particles thus obtained is the average particle size of the powder. As the transmission electron microscope, for example, a Hitachi transmission electron microscope H-9000 type can be used. The particle size can be measured using known image analysis software, for example, Carl Zeiss image analysis software KS-400. The average particle size shown in the examples described below is a value measured using a Hitachi transmission electron microscope H-9000 type as the transmission electron microscope and Carl Zeiss image analysis software KS-400 as the image analysis software, unless otherwise specified. In the present invention and this specification, powder means a collection of multiple particles. For example, ferromagnetic powder means a collection of multiple ferromagnetic particles. In addition, the collection of multiple particles is not limited to a form in which the particles constituting the collection are in direct contact with each other, and also includes a form in which a binder, additive, etc., described later, are interposed between the particles. The term particle is sometimes used to refer to powder.
[0140] As a method for collecting a sample powder from a magnetic recording medium for particle size measurement, for example, the method described in paragraph 0015 of JP 2011-048878 A can be used.
[0141] In the present invention and this specification, unless otherwise specified, the size of the particles constituting the powder (particle size) is determined by the shape of the particles observed in the particle photograph. (1) In the case of needle-shaped, spindle-shaped, columnar (where the height is greater than the maximum major axis of the base), etc., it is expressed by the length of the major axis that constitutes the particle, i.e., the major axis length. (2) In the case of a plate or columnar shape (where the thickness or height is smaller than the maximum long diameter of the plate or base), it shall be expressed by the maximum long diameter of the plate or base. (3) In the case of a particle having a spherical, polyhedral, or unspecified shape, and the major axis of the particle cannot be specified from its shape, the particle is expressed as the equivalent circle diameter, which is determined by the circle projection method.
[0142] The average acicular ratio of a powder refers to the arithmetic average of the short axis length of the particles, i.e., the short axis length, the (long axis length / short axis length) value of each particle, and the values obtained for the 500 particles. Here, unless otherwise specified, the short axis length refers to the length of the short axis constituting the particle in the above definition of particle size (1), and to the thickness or height in the above definition of particle size (2), and in the above definition of particle size (3), since there is no distinction between the long axis and the short axis, (long axis length / short axis length) is considered to be 1 for the sake of convenience. Unless otherwise specified, when the particle shape is specific, for example, in the case of the above definition of particle size (1), the average particle size is the average major axis length, in the case of definition (2), the average particle size is the average plate diameter, and in the case of definition (3), the average particle size is the average diameter (also called the average particle diameter or average particle size).
[0143] The content (filling rate) of the ferromagnetic powder in the magnetic layer is preferably in the range of 50 to 90 mass % relative to the total mass of the magnetic layer, and more preferably in the range of 60 to 90 mass %. The magnetic layer contains ferromagnetic powder, may contain a binder, and may optionally contain one or more further additives. A high filling rate of the ferromagnetic powder in the magnetic layer is preferable from the viewpoint of improving recording density.
[0144] (Binding agent, hardener) The magnetic recording medium may be a coating type magnetic recording medium, and the magnetic layer may contain a binder. The binder is one or more kinds of resin. As the binder, various resins that are usually used as binders for coating type magnetic recording media may be used. For example, as the binder, a resin selected from polyurethane resin, polyester resin, polyamide resin, vinyl chloride resin, acrylic resin copolymerized with styrene, acrylonitrile, methyl methacrylate, etc., cellulose resin such as nitrocellulose, epoxy resin, phenoxy resin, polyvinyl acetal, polyvinyl butyral, etc. may be used alone or in combination of a plurality of resins. Among these, polyurethane resin, acrylic resin, cellulose resin, and vinyl chloride resin are preferred. These resins may be homopolymers or copolymers. These resins may also be used as binders in the non-magnetic layer and / or backcoat layer described later. For the above binders, refer to paragraphs 0028 to 0031 of JP-A-2010-24113. The content of the binder in the magnetic layer can be, for example, 1.0 to 30.0 parts by mass relative to 100.0 parts by mass of the ferromagnetic powder. The average molecular weight of the resin used as the binder can be, for example, 10,000 or more and 200,000 or less in weight average molecular weight. The weight average molecular weight described in the Examples section below is, unless otherwise specified, a value measured by gel permeation chromatography (GPC) under the following measurement conditions and calculated in terms of standard polystyrene. The binder can be used in an amount of, for example, 1.0 to 30.0 parts by mass relative to 100.0 parts by mass of the ferromagnetic powder. GPC equipment: HLC-8120 (Tosoh Corporation) Column: TSK gel Multipore HXL-M (Tosoh Corporation, 7.8 mm ID (inner diameter) × 30.0 cm) Eluent: tetrahydrofuran (THF)
[0145] A curing agent can also be used together with the resin usable as a binder. In one embodiment, the curing agent can be a thermosetting compound that undergoes a curing reaction (crosslinking reaction) by heating, and in another embodiment, a photocuring compound that undergoes a curing reaction (crosslinking reaction) by irradiation with light. The curing agent can be included in the magnetic layer in a state where at least a part of the curing agent reacts (crosslinks) with other components such as the binder as the curing reaction proceeds during the magnetic layer forming process. This point is also true for layers formed using a composition used to form other layers that contains a curing agent. A preferred curing agent is a thermosetting compound, and polyisocyanate is suitable. For details about polyisocyanate, refer to paragraphs 0124 to 0125 of JP 2011-216149 A. The content of the curing agent in the magnetic layer forming composition can be, for example, 0 to 80.0 parts by mass relative to 100.0 parts by mass of the binder, and can be 50.0 to 80.0 parts by mass from the viewpoint of improving the strength of the magnetic layer.
[0146] (Additives) The magnetic layer may contain one or more additives as necessary. An example of the additive is the curing agent. Examples of the additives contained in the magnetic layer include non-magnetic powder, lubricant, dispersant, dispersion aid, antifungal agent, antistatic agent, antioxidant, and the like. For the dispersant, refer to paragraphs 0061 and 0071 of JP-A-2012-133837. The dispersant may be added to the non-magnetic layer forming composition. For the dispersant that can be added to the non-magnetic layer forming composition, refer to paragraph 0061 of JP-A-2012-133837. Examples of the non-magnetic powder that can be contained in the magnetic layer include non-magnetic powder that can function as an abrasive, non-magnetic powder that can function as a protrusion forming agent that forms protrusions that protrude appropriately on the magnetic layer surface, and the like. Examples of the abrasive include powders of alumina (Al2O3), silicon carbide, boron carbide (B4C), TiC, chromium oxide (Cr2O3), cerium oxide, zirconium oxide (ZrO2), iron oxide, diamond, etc., which are materials usually used as abrasives for magnetic layers, and among these, powders of alumina such as α-alumina, silicon carbide, and diamond are preferred. The content of the abrasive in the magnetic layer is preferably 1.0 to 20.0 parts by mass, more preferably 3.0 to 15.0 parts by mass, and even more preferably 4.0 to 10.0 parts by mass, relative to 100.0 parts by mass of ferromagnetic powder. The average particle size of the abrasive is, for example, in the range of 30 to 300 nm, and preferably in the range of 50 to 200 nm. Examples of the protrusion-forming agent include carbon black and colloidal particles. The content of the protrusion-forming agent in the magnetic layer is preferably 0.1 to 10.0 parts by mass, more preferably 0.1 to 5.0 parts by mass, and even more preferably 0.5 to 5.0 parts by mass, relative to 100.0 parts by mass of the ferromagnetic powder. The average particle size of the colloidal particles is preferably in the range of, for example, 90 to 200 nm, and more preferably in the range of 100 to 150 nm. The average particle size of the carbon black is preferably in the range of 5 to 200 nm, and more preferably in the range of 10 to 150 nm.
[0147] The magnetic recording medium may contain at least one fatty acid compound selected from the group consisting of fatty acids, fatty acid esters, and fatty acid amides in the magnetic layer on the non-magnetic support. The fatty acid compound may function as a lubricant. The magnetic layer may contain only one fatty acid compound selected from the group consisting of fatty acids, fatty acid esters, and fatty acid amides, or may contain two or more fatty acids. The fatty acid may contain only one or two or more fatty acids. This also applies to fatty acid esters and fatty acid amides. Examples of fatty acids include lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, behenic acid, erucic acid, elaidic acid, etc., with stearic acid, myristic acid, palmitic acid, etc. being preferred, and stearic acid being more preferred. The fatty acid may be contained in the magnetic layer in the form of a salt such as a metal salt. Examples of fatty acid esters include esters of the various fatty acids exemplified above, etc. Specific examples include butyl myristate, butyl palmitate, butyl stearate (butyl stearate), neopentyl glycol dioleate, sorbitan monostearate, sorbitan distearate, sorbitan tristearate, oleyl oleate, isocetyl stearate, isotridecyl stearate, octyl stearate, isooctyl stearate, amyl stearate, butoxyethyl stearate, etc. Examples of the fatty acid amide include amides of the various fatty acids exemplified above, such as lauric acid amide, myristic acid amide, palmitic acid amide, and stearic acid amide. As for fatty acids and fatty acid derivatives (amides, esters, etc.), it is preferable that the fatty acid-derived portion of the fatty acid derivative has the same or similar structure as the fatty acid used in combination. For example, when stearic acid is used as the fatty acid, it is preferable to use stearic acid amide and / or stearic acid ester in combination. In one embodiment, a magnetic recording medium containing one or more fatty acid compounds selected from the group consisting of fatty acids, fatty acid esters, and fatty acid amides in the magnetic layer side can be manufactured by forming a magnetic layer using a magnetic layer forming composition containing one or more of the fatty acid compounds. In another embodiment, a magnetic recording medium containing one or more of the fatty acid compounds in the magnetic layer side can be manufactured by forming a nonmagnetic layer using a nonmagnetic layer forming composition containing one or more of the fatty acid compounds. In another embodiment, a magnetic recording medium containing one or more of the fatty acid compounds in the magnetic layer side can be manufactured by forming a nonmagnetic layer using a nonmagnetic layer forming composition containing one or more of the fatty acid compounds and forming a magnetic layer using a magnetic layer forming composition containing one or more of the fatty acid compounds. The nonmagnetic layer can play a role of retaining components that can function as lubricants such as fatty acids, fatty acid esters, and fatty acid amides and supplying them to the magnetic layer. Lubricants such as fatty acids, fatty acid esters, and fatty acid amides contained in the nonmagnetic layer can migrate to the magnetic layer and exist in the magnetic layer. The content of fatty acid in the magnetic layer or in the composition for forming the magnetic layer is preferably 0.5 to 3.0 parts by mass per 100.0 parts by mass of ferromagnetic powder. The content of the fatty acid ester in the magnetic layer or in the composition for forming the magnetic layer is, for example, 0 to 10.0 parts by mass, and preferably 0.5 to 7.0 parts by mass, per 100.0 parts by mass of the ferromagnetic powder. The content of the fatty acid amide in the magnetic layer or in the composition for forming the magnetic layer is, for example, 0 to 1.0 part by mass, and preferably 0.1 to 1.0 part by mass, per 100.0 parts by mass of the ferromagnetic powder. Regarding the contents of fatty acids, fatty acid esters and fatty acid amides in the nonmagnetic layer or the composition for forming the nonmagnetic layer, the above description can be applied by replacing the ferromagnetic powder with the nonmagnetic powder. Regarding the mixing ratio of the silicon-containing compound and the fatty acid compound in the magnetic layer or the composition for forming the magnetic layer, the total amount (mass basis) of the silicon-containing compound and the fatty acid compound is taken as 100 mass%, and the ratio of the fatty acid compound can be 10 mass% or more, 15 mass% or more, 20 mass% or more, 25 mass% or more, or 30 mass% or more, and can be 90 mass% or less, 80 mass% or less, 70 mass% or less, 60 mass% or less, or 50 mass% or less. The above points also apply to the mixing ratio of the silicon-containing compound and the fatty acid compound in the nonmagnetic layer or the composition for forming the nonmagnetic layer.
[0148] The magnetic layer described above can be provided directly on the surface of the non-magnetic support, or indirectly via a non-magnetic layer.
[0149] <Nonmagnetic layer> Next, the non-magnetic layer will be described. The magnetic recording medium may have a magnetic layer directly on the surface of the non-magnetic support, or may have a magnetic layer on the surface of the non-magnetic support via a non-magnetic layer containing non-magnetic powder. The non-magnetic powder used in the non-magnetic layer may be an inorganic powder or an organic powder. Carbon black or the like can also be used. Examples of inorganic powders include powders of metals, metal oxides, metal carbonates, metal sulfates, metal nitrides, metal carbides, metal sulfides, and the like. These non-magnetic powders are commercially available, and can also be produced by known methods. For details, refer to paragraphs 0146 to 0150 of JP-A-2011-216149. For carbon black usable in the non-magnetic layer, refer to paragraphs 0040 to 0041 of JP-A-2010-24113. The content (filling rate) of the non-magnetic powder in the non-magnetic layer is preferably in the range of 50 to 90% by mass, more preferably in the range of 60 to 90% by mass, based on the total mass of the non-magnetic layer.
[0150] The non-magnetic layer may be a layer containing a non-magnetic powder and a binder, and may further contain one or more additives. For other details of the binder, additives, etc. of the non-magnetic layer, known techniques related to non-magnetic layers can be applied. In addition, for example, for the type and content of the binder, the type and content of the additives, known techniques related to magnetic layers can also be applied.
[0151] In the present invention and this specification, the nonmagnetic layer also includes a substantially nonmagnetic layer that contains a small amount of ferromagnetic powder, for example as an impurity or intentionally, along with a nonmagnetic powder. A substantially nonmagnetic layer here refers to a layer whose residual magnetic flux density is 10 mT or less, whose coercive force is 100 Oe or less, or whose residual magnetic flux density is 10 mT or less and whose coercive force is 100 Oe or less. 1 [kOe] = 10 6 / 4π[A / m]. It is preferable that the nonmagnetic layer has no residual magnetic flux density and no coercive force.
[0152] <Nonmagnetic support> Next, the non-magnetic support (hereinafter, simply referred to as "support") will be described. Examples of the non-magnetic support include known biaxially stretched polyethylene terephthalate, polyethylene naphthalate, polyamide, polyamideimide, aromatic polyamide, and the like. Among these, polyethylene terephthalate, polyethylene naphthalate, and polyamide are preferred. These supports may be previously subjected to corona discharge, plasma treatment, easy-adhesion treatment, heat treatment, and the like.
[0153] <Backcoat layer> The magnetic recording medium may also have a backcoat layer containing a nonmagnetic powder on the surface side opposite to the surface side having the magnetic layer of the nonmagnetic support. The backcoat layer preferably contains either or both of carbon black and inorganic powder. The backcoat layer may be a layer containing a nonmagnetic powder and a binder, and may further contain one or more additives. For the binder of the backcoat layer and various additives that may be optionally contained therein, known techniques related to the backcoat layer may be applied, and known techniques related to the formulation of the magnetic layer and / or the nonmagnetic layer may also be applied. For example, the descriptions in paragraphs 0018-0020 of JP 2006-331625 A and in column 4, line 65 to column 5, line 38 of the specification of U.S. Pat. No. 7,029,774 may be referred to for the backcoat layer.
[0154] <Contact angle> In one embodiment, the contact angle of water measured on the surface of the magnetic layer of the magnetic recording medium can be 90° or more.The inventor believes that the contact angle can be an indicator of the amount of the silicon-containing compound present in the magnetic layer side portion.The inventor believes that the amount of the silicon-containing compound present in the magnetic layer side portion is preferably such that the contact angle is 90° or more, in order to further reduce the friction coefficient after repeated running, and is also preferably for further suppressing the change in the surface shape of the magnetic layer before and after repeated running.
[0155] In the present invention and this specification, the contact angle with water measured on the surface of the magnetic layer is determined by the following method. In the present invention and this specification, the "surface of the magnetic layer" is synonymous with the magnetic layer side surface of the magnetic recording medium.
[0156] (Contact angle measurement) The contact angle is determined by dropping water onto a measurement point on the surface of the magnetic layer of the magnetic recording medium to be measured in a measurement environment with an ambient temperature of 20°C and a relative humidity of 25%, and using the θ / 2 method. An example of the measurement conditions will be described later in the Examples section. The measurement points are six randomly selected points on the surface of the magnetic layer, and the contact angle is measured at each of the six points. The arithmetic average of the six measured values thus obtained is regarded as the contact angle with water measured on the surface of the magnetic layer of the magnetic recording medium to be measured.
[0157] The contact angle of the magnetic recording medium is preferably 90° or more, and may be 95° or more or 100° or more. From the viewpoint of maintaining the strength of the magnetic layer, the contact angle of the magnetic recording medium is preferably 120° or less, more preferably 115° or less, and even more preferably 110° or less. The unit of angle "°" is also written as degree.
[0158] The contact angle of magnetic recording medium can be controlled by the amount of the silicon-containing compound used for the production of magnetic recording medium.In addition, the contact angle of magnetic recording medium can be controlled by the amount of the nitrogen-containing raw material polymer and the silicon-containing raw material compound used in the production process of magnetic recording medium, which can form the nitrogen-containing polymer having the partial structure represented by formula 1.
[0159] <Various thicknesses> The thickness of the nonmagnetic support is, for example, 3.0 to 80.0 μm, preferably 3.0 to 20.0 μm, more preferably 3.0 to 10.0 μm, and even more preferably 3.0 to 6.0 μm.
[0160] The thickness of the magnetic layer can be optimized according to the saturation magnetization amount of the magnetic head used, the head gap length, the band of the recording signal, etc. From the viewpoint of high density recording, the thickness of the magnetic layer is preferably 10 nm to 150 nm, more preferably 20 nm to 120 nm, and even more preferably 30 nm to 100 nm. There should be at least one magnetic layer, and the magnetic layer may be separated into two or more layers having different magnetic properties, and a known configuration related to a multilayer magnetic layer can be applied. When the magnetic layer is separated into two or more layers, the thickness of the magnetic layer is the total thickness of these layers.
[0161] The thickness of the nonmagnetic layer is, for example, 0.1 to 3.0 μm, preferably 0.1 to 2.0 μm, and more preferably 0.1 to 1.5 μm.
[0162] The thickness of the backcoat layer is preferably 0.9 μm or less, and more preferably in the range of 0.1 to 0.7 μm.
[0163] The thickness of each layer of the magnetic recording medium and the non-magnetic support can be determined by a known film thickness measurement method. For example, the cross section of the magnetic recording medium in the thickness direction is exposed by a known method such as ion beam or microtome, and then the exposed cross section is observed by a scanning electron microscope or a transmission electron microscope. Various thicknesses can be determined as the thickness determined at any one point in the cross section observation, or the arithmetic average of the thicknesses determined at two or more randomly selected points, for example, two points. Alternatively, the thickness of each layer may be determined as a design thickness calculated from the manufacturing conditions.
[0164] <Method of manufacturing magnetic recording medium> The process of preparing the composition for forming the magnetic layer, and the optional non-magnetic layer and backcoat layer can usually include at least a kneading process, a dispersion process, and a mixing process provided before or after these processes as necessary. Each of the individual processes may be divided into two or more stages. The components used in the preparation of each layer-forming composition may be added at the beginning or during any process. Also, each raw material may be added in portions in two or more processes. As described above, one or more nitrogen-containing raw material polymers and one or more silicon-containing raw material compounds are used as components of the magnetic layer-forming composition, and by mixing them in the preparation process of the magnetic layer-forming composition, a nitrogen-containing polymer having a partial structure represented by formula 1 can be formed. In one embodiment, one or more nitrogen-containing raw material polymers and one or more silicon-containing raw material compounds are mixed before the preparation of the magnetic layer-forming composition to form a nitrogen-containing polymer having a partial structure represented by formula 1, and then this polymer can be used as a component of the magnetic layer-forming composition to prepare the magnetic layer-forming composition. This point also applies to the preparation process of the non-magnetic layer-forming composition. In order to prepare each layer-forming composition, a known technique can be used. In the kneading step, it is preferable to use a kneader having a strong kneading force, such as an open kneader, a continuous kneader, a pressure kneader, or an extruder. Details of these kneading processes are described in JP-A-1-106338 and JP-A-1-79274. In addition, in order to disperse each layer-forming composition, one or more types of dispersion beads selected from the group consisting of glass beads and other dispersion beads can be used as a dispersion medium. As such dispersion beads, zirconia beads, titania beads, and steel beads, which are dispersion beads with high specific gravity, are suitable. The particle size (bead diameter) and packing rate of these dispersion beads can be optimized for use. A known dispersing machine can be used. Each layer-forming composition may be filtered by a known method before being subjected to the coating step. Filtration can be performed, for example, by filter filtration. As the filter used for filtration, for example, a filter with a pore size of 0.01 to 3 μm (for example, a glass fiber filter, a polypropylene filter, etc.) can be used.
[0165] The magnetic layer can be formed by applying the magnetic layer-forming composition directly onto the surface of the non-magnetic support, or by applying the magnetic layer-forming composition successively or simultaneously in a multilayer manner with the non-magnetic layer-forming composition. The backcoat layer can be formed by applying the backcoat layer-forming composition onto the surface of the non-magnetic support opposite to the surface on which the magnetic layer is provided (or will be provided later).
[0166] After the coating step, various treatments such as drying, orientation of the magnetic layer, and surface smoothing (calendering) can be performed. For the coating step and various treatments, known techniques can be applied, and for example, refer to paragraphs 0051 to 0057 of JP-A-2010-24113. For example, vertical orientation can be performed as the orientation. The vertical orientation can be performed by known methods such as a method using magnets with opposite poles facing each other. In the orientation zone, the drying speed of the coating layer can be controlled by the temperature and volume of the drying air and / or the transport speed of the magnetic recording medium in the orientation zone. In addition, the coating layer may be pre-dried before being transported to the orientation zone.
[0167] In the magnetic recording medium manufactured as described above, a servo pattern can be formed by a known method in order to enable tracking control of a magnetic head in a magnetic recording and reproducing device, control of the running speed of the magnetic recording medium, and the like. "Formation of a servo pattern" can also be called "recording of a servo signal." The magnetic recording medium may be a tape-shaped magnetic recording medium (magnetic tape) or a disk-shaped magnetic recording medium (magnetic disk). The formation of a servo pattern will be described below using a magnetic tape as an example.
[0168] The servo pattern is usually formed along the longitudinal direction of the magnetic tape. Control methods that use servo signals (servo control) include timing-based servo (TBS), amplitude servo, and frequency servo.
[0169] As shown in ECMA (European Computer Manufacturers Association)-319, a magnetic tape (generally called "LTO tape") conforming to the LTO (Linear Tape-Open) standard employs a timing-based servo system. In this timing-based servo system, a servo pattern is formed by a pair of non-parallel magnetic stripes (also called "servo stripes") arranged continuously in the longitudinal direction of the magnetic tape. As described above, the reason why the servo pattern is formed by a pair of non-parallel magnetic stripes is to inform the servo signal reading element passing over the servo pattern of its passing position. Specifically, the pair of magnetic stripes is formed so that the interval between them changes continuously along the width direction of the magnetic tape, and the servo signal reading element can know the relative position between the servo pattern and the servo signal reading element by reading the interval. This relative position information enables tracking of the data track. For this purpose, a plurality of servo tracks are usually set on the servo pattern along the width direction of the magnetic tape.
[0170] A servo band is made up of a series of servo signals along the length of the magnetic tape. Usually, multiple servo bands are provided on a magnetic tape. For example, there are five servo bands on an LTO tape. The area between two adjacent servo bands is called a data band. A data band is made up of multiple data tracks, and each data track corresponds to one servo track.
[0171] Also, in one embodiment, as shown in JP 2004-318983 A, information indicating the number of the servo band (also called "servo band ID (identification)" or "UDIM (Unique Data Band Identification Method) information") is embedded in each servo band. This servo band ID is recorded by shifting a specific one of a plurality of pairs of servo stripes in the servo band so that its position is displaced relatively in the longitudinal direction of the magnetic tape. Specifically, the way in which a specific one of a plurality of pairs of servo stripes is shifted is changed for each servo band. As a result, the recorded servo band ID is unique for each servo band, so that the servo band can be uniquely identified simply by reading one servo band with a servo signal reading element.
[0172] As a method for uniquely identifying servo bands, there is also a method using the staggered method as specified in ECMA-319. In this staggered method, a group of pairs of non-parallel magnetic stripes (servo stripes) arranged continuously in the longitudinal direction of the magnetic tape are recorded so that they are shifted in the longitudinal direction of the magnetic tape for each servo band. Since the combination of the shift between adjacent servo bands is unique across the entire magnetic tape, it is possible to uniquely identify the servo bands when reading the servo pattern with two servo signal reading elements.
[0173] Also, as specified in ECMA-319, information indicating the longitudinal position of the magnetic tape (also called "LPOS (Longitudinal Position) information") is usually embedded in each servo band. Like UDIM information, this LPOS information is also recorded by shifting the positions of a pair of servo stripes in the longitudinal direction of the magnetic tape. However, unlike UDIM information, the same signal is recorded in each servo band with this LPOS information.
[0174] It is also possible to embed information other than the above UDIM information and LPOS information in the servo bands. In this case, the embedded information may be different for each servo band, such as UDIM information, or may be common to all servo bands, such as LPOS information. Also, methods other than those described above can be used to embed information in the servo bands. For example, a predetermined code may be recorded by thinning out a predetermined pair from a group of pairs of servo stripes.
[0175] The head for forming a servo pattern is called a servo write head. The servo write head has a pair of gaps corresponding to the pair of magnetic stripes, the number of which is equal to the number of servo bands. Usually, a core and a coil are connected to each pair of gaps, and a magnetic field generated in the core can generate a leakage magnetic field in the pair of gaps by supplying a current pulse to the coil. When forming a servo pattern, a magnetic pattern corresponding to the pair of gaps can be transferred to the magnetic tape by inputting a current pulse while running the magnetic tape on the servo write head, thereby forming the servo pattern. The width of each gap can be appropriately set according to the density of the servo pattern to be formed. The width of each gap can be set, for example, to 1 μm or less, 1 to 10 μm, or 10 μm or more.
[0176] Before forming a servo pattern on the magnetic tape, the magnetic tape is usually subjected to a demagnetization (erase) process. This erase process can be performed by applying a uniform magnetic field to the magnetic tape using a direct current magnet or an alternating current magnet. There are two types of erase processes: DC (Direct Current) erase and AC (Alternating Current) erase. AC erase is performed by gradually lowering the strength of the magnetic field applied to the magnetic tape while reversing the direction of the magnetic field. On the other hand, DC erase is performed by applying a unidirectional magnetic field to the magnetic tape. There are two more methods of DC erase. The first method is horizontal DC erase, which applies a unidirectional magnetic field along the longitudinal direction of the magnetic tape. The second method is vertical DC erase, which applies a unidirectional magnetic field along the thickness direction of the magnetic tape. The erase process may be performed on the entire magnetic tape, or may be performed for each servo band of the magnetic tape.
[0177] The direction of the magnetic field of the formed servo pattern is determined according to the direction of erasure. For example, when the magnetic tape is subjected to horizontal DC erasure, the servo pattern is formed so that the direction of the magnetic field is opposite to the direction of erasure. This makes it possible to increase the output of the servo signal obtained by reading the servo pattern. As shown in JP2012-53940A, when the magnetic pattern is transferred to the magnetic tape that has been vertically DC erased using the above gap, the servo signal obtained by reading the formed servo pattern has a unipolar pulse shape. On the other hand, when the magnetic pattern is transferred to the magnetic tape that has been horizontally DC erased using the above gap, the servo signal obtained by reading the formed servo pattern has a bipolar pulse shape.
[0178] [Magnetic tape cartridge] One aspect of the present invention relates to a magnetic tape cartridge including the above-mentioned magnetic recording medium in tape form (that is, a magnetic tape).
[0179] The details of the magnetic tape contained in the magnetic tape cartridge are as described above.
[0180] In a magnetic tape cartridge, the magnetic tape is generally accommodated inside the cartridge body in a state where it is wound around a reel. The reel is provided rotatably inside the cartridge body. As the magnetic tape cartridge, a single-reel type magnetic tape cartridge having one reel inside the cartridge body and a twin-reel type magnetic tape cartridge having two reels inside the cartridge body are widely used. When a single-reel type magnetic tape cartridge is loaded into a magnetic recording and reproducing device for recording and / or reproducing data on the magnetic tape, the magnetic tape is pulled out from the magnetic tape cartridge and wound around the reel on the magnetic recording and reproducing device side. A magnetic head is disposed on the magnetic tape transport path from the magnetic tape cartridge to the take-up reel. The magnetic tape is fed and wound between the reel (supply reel) on the magnetic tape cartridge side and the reel (take-up reel) on the magnetic recording and reproducing device side. During this time, the magnetic head comes into contact with and slides on the surface of the magnetic layer side of the magnetic tape, thereby recording and / or reproducing data. In contrast, a dual-reel magnetic tape cartridge has both a supply reel and a take-up reel inside the magnetic tape cartridge. The magnetic tape cartridge may be either a single-reel or dual-reel magnetic tape cartridge. The magnetic tape cartridge may include the magnetic tape according to one aspect of the present invention, and other aspects may be based on known techniques.
[0181] [Magnetic recording and playback device] One aspect of the present invention relates to a magnetic recording and reproducing device including the above magnetic recording medium.
[0182] In the present invention and this specification, the term "magnetic recording and reproducing device" refers to a device capable of at least one of recording data to a magnetic recording medium and reproducing data recorded on the magnetic recording medium. Such a device is generally called a drive. The magnetic recording and reproducing device may be, for example, a sliding type magnetic recording and reproducing device. The sliding type magnetic recording and reproducing device refers to a device in which the surface of the magnetic layer and a magnetic head come into contact and slide when recording data on the magnetic recording medium and / or reproducing the recorded data. For example, the magnetic recording and reproducing device may include the magnetic tape cartridge in a removable manner.
[0183] The magnetic recording and reproducing device may include a magnetic head. The magnetic head may be a recording head capable of recording data on a magnetic recording medium, or may be a reproducing head capable of reproducing data recorded on the magnetic recording medium. In one embodiment, the magnetic recording and reproducing device may include both a recording head and a reproducing head as separate magnetic heads. In another embodiment, the magnetic head included in the magnetic recording and reproducing device may have a configuration in which both an element for recording data (recording element) and an element for reproducing data (reproducing element) are provided in one magnetic head. Hereinafter, the element for recording data and the element for reproducing data are collectively referred to as "data element". As the reproducing head, a magnetic head (MR head) including a magnetoresistive (MR) element capable of reading data recorded on a magnetic recording medium with good sensitivity as a reproducing element is preferable. As the MR head, various known MR heads such as an anisotropic magnetoresistive (AMR) head, a giant magnetoresistive (GMR) head, and a tunnel magnetoresistive (TMR) head may be used. Also, the magnetic head that records and / or reproduces data may include a servo signal read element. Alternatively, the magnetic recording and reproducing device may include a magnetic head (servo head) equipped with a servo signal read element as a head separate from the magnetic head that records and / or reproduces data. For example, a magnetic head that records and / or reproduces recorded data (hereinafter also referred to as a "recording and reproducing head") may include two servo signal read elements, and each of the two servo signal read elements can simultaneously read two adjacent servo bands. One or more data elements may be disposed between the two servo signal read elements.
[0184] In the magnetic recording and reproducing device, the recording of data on the magnetic recording medium and / or the reproduction of data recorded on the magnetic recording medium can be performed, for example, by contacting and sliding the magnetic head against the surface of the magnetic recording medium on the magnetic layer side. The magnetic recording and reproducing device may include the magnetic recording medium according to one embodiment of the present invention, and other known techniques may be applied.
[0185] For example, when recording data and / or reproducing recorded data, tracking using servo signals is first performed. That is, the servo signal reading element is made to follow a specific servo track, so that the data element passes over the target data track. The data track is moved by changing the servo track read by the servo signal reading element in the tape width direction. The recording / reproducing head can also record and / or reproduce data on other data bands by using the UDIM information described above to move the servo signal reading element to a specific servo band and start tracking on that servo band. EXAMPLES
[0186] An embodiment of the present invention will be described below based on an example. However, the present invention is not limited to the embodiment shown in the example. The indications of "parts" and "%" below mean "parts by mass" and "% by mass" unless otherwise specified. "eq" is an equivalent, and is a unit that cannot be converted to SI units. In addition, the following various steps and operations were carried out in an environment with a temperature of 20 to 25° C. and a relative humidity of 40 to 60%, unless otherwise specified.
[0187] [Ferromagnetic powder] In the examples and comparative examples, the following hexagonal strontium ferrite was used as the ferromagnetic powder.
[0188] 1707 g of SrCO3, 687 g of H3BO3, 1120 g of Fe2O3, 45 g of Al(OH)3, 24 g of BaCO3, 13 g of CaCO3, and 235 g of Nd2O3 were weighed out and mixed in a mixer to obtain a raw material mixture. The obtained raw material mixture was melted in a platinum crucible at a melting temperature of 1390°C, and the melt was poured into a rod shape at about 6 g / sec by heating the tapping hole at the bottom of the platinum crucible while stirring the melt. The tapped liquid was rolled and quenched with a water-cooled twin roller to produce an amorphous body. 280 g of the produced amorphous body was placed in an electric furnace, heated to 635°C (crystallization temperature) at a heating rate of 3.5°C / min, and held at that temperature for 5 hours to precipitate (crystallize) hexagonal strontium ferrite particles. Next, the crystallized material obtained above containing hexagonal strontium ferrite particles was coarsely crushed in a mortar, and 1000g of zirconia beads with a particle size of 1mm and 800mL of 1% aqueous acetic acid solution were added to the glass bottle containing the crushed material, and the mixture was dispersed for 3 hours using a paint shaker. The resulting dispersion was then separated from the beads and placed in a stainless steel beaker. The dispersion was left to stand at a liquid temperature of 100°C for 3 hours to dissolve the glass components, and then precipitated in a centrifuge and washed by repeated decantation, and dried for 6 hours in a heating furnace at a furnace temperature of 110°C to obtain hexagonal strontium ferrite powder. The average particle size of the hexagonal strontium ferrite powder obtained above is 18 nm, and the activation volume is 902 nm. 3 , the anisotropy constant Ku is 2.2×10 5 J / m 3 , mass magnetization σs is 49A m 2 / kg. A 12 mg sample powder was taken from the hexagonal strontium ferrite powder obtained above, and this sample powder was partially dissolved under the dissolution conditions exemplified above. The elemental analysis of the filtrate obtained was performed using an ICP analyzer to determine the surface layer content of neodymium atoms. Separately, 12 mg of sample powder was taken from the hexagonal strontium ferrite powder obtained above, and this sample powder was completely dissolved under the dissolution conditions exemplified above. The elemental analysis of the filtrate obtained was performed using an ICP analyzer to determine the bulk content of neodymium atoms. The neodymium atom content (bulk content) relative to 100 atomic % of iron atoms in the hexagonal strontium ferrite powder obtained above was 2.9 atomic %. The surface layer content of neodymium atoms was 8.0 atomic %. The ratio of the surface layer content to the bulk content, "surface layer content / bulk content," was 2.8, confirming that neodymium atoms were unevenly distributed in the surface layers of the particles.
[0189] It was confirmed that the powder obtained above exhibited a hexagonal ferrite crystal structure by scanning with CuKα radiation at a voltage of 45 kV and an intensity of 40 mA and measuring the X-ray diffraction pattern under the following conditions (X-ray diffraction analysis). The powder obtained above exhibited a magnetoplumbite-type (M-type) hexagonal ferrite crystal structure. The crystal phase detected by the X-ray diffraction analysis was a single phase of magnetoplumbite type. PANalytical X'Pert Pro diffractometer, PIXcel detector Soller slits for incident and diffracted beams: 0.017 radians Dispersion slit fixed angle: 1 / 4 degree Mask: 10mm Anti-scatter slit: 1 / 4 degree Measurement mode: Continuous Measurement time per step: 3 seconds Measurement speed: 0.017 degrees per second Measurement step: 0.05 degrees
[0190] The activation volume and anisotropy constant Ku of the above hexagonal strontium ferrite powder are values determined for each ferromagnetic powder by the method described above using a vibrating sample magnetometer (manufactured by Toei Kogyo Co., Ltd.). The mass magnetization σs is a value measured using a vibrating sample magnetometer (manufactured by Toei Industry Co., Ltd.) at a magnetic field strength of 1194 kA / m (15 kOe).
[0191] [Synthesis of polymer having constitutional unit represented by formula 2] In the following, the monomer containing a silicon atom is referred to as "monomer a" and the other monomer is referred to as "monomer b". The polymers P-1 to P-4 shown above were each synthesized by the method described below. The fact that the polymers P-1 to P-4 were synthesized can be understood as follows. 1 H-NMR (Nuclear Magnetic Resonance) and 13 This was confirmed by the results of both 1C-NMR and 1C-NMR analyses.
[0192] <Synthesis of Polymer P-1> 15.0 g of cyclohexanone was placed in a 200 mL three-neck flask equipped with a stirrer, a cooling tube, a nitrogen inlet tube, and a thermometer, and the inside temperature was adjusted to 80 ° C. and replaced with nitrogen. A solution of 30.0 g of monomer K-1 (X-22-2404 manufactured by Shin-Etsu Chemical Co., Ltd.) previously shown as monomer a, 0.2 g of 2,2'-azobis(isobutyric acid) dimethyl (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 30.0 g of cyclohexanone was dropped over 3 hours. A mixed solution of 0.2 g of 2,2'-azobis(isobutyric acid) dimethyl and 2.5 g of cyclohexanone was added, and the mixture was stirred at an inside temperature of 90 ° C. for 3 hours, and then 22.5 g of cyclohexanone was added to obtain polymer P-1.
[0193] <Synthesis of polymer P-2> Polymer P-2 was synthesized as described above for the synthesis of polymer P-1, except that monomer K-1 was replaced with monomer K-1 (monomer a) and methacrylic acid (monomer b). Table 1 below shows the mixing ratio (molar ratio) of monomer a and monomer b. In Table 1, the values in the "a" and "b" columns are the mixing ratios (molar ratios).
[0194] <Synthesis of polymer P-3> Polymer P-3 was synthesized as described above for the synthesis of polymer P-1, except that monomer K-1 was replaced with monomer K-1 (monomer a) and 2-aminoethyl methacrylate (monomer b). Table 1 below shows the mixing ratio (molar ratio) of monomer a and monomer b.
[0195] <Synthesis of polymer P-4> Polymer P-2 was synthesized as described above for the synthesis of polymer P-1, except that monomer K-1 was replaced with monomer K-1 (monomer a) and 2-hydroxyethyl methacrylate (monomer b). Table 1 below shows the mixing ratio (molar ratio) of monomer a and monomer b.
[0196] [Synthesis of Comparative Polymer Not Having the Partial Structure Represented by Formula 1] <Synthesis of Comparative Polymer R-1> Comparative polymer R-1 was synthesized as described above for the synthesis of polymer P-1, except that monomer K-1 was replaced with monomer r-1 shown below.
[0197] [ka]
[0198] R-1 is a homopolymer containing the structural unit shown below, and is a polymer that does not have the partial structure represented by formula 1.
[0199] [ka]
[0200] [Synthesis of nitrogen-containing polymer (polyalkyleneimine polymer) having a partial structure represented by formula 1] <Synthesis of polyalkyleneimine polymer Q-1> In a 500mL three-neck flask, 16.8g of n-octanoic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a carboxylic acid, 100g of ε-caprolactone (Daicel Industrial Chemical Industries, Ltd., Plaxel M) as a lactone, and 2.2g of monobutyltin oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (C4H9Sn(O)OH) as a catalyst were mixed and heated at a temperature of 160°C for 1 hour. 100g of ε-caprolactone was added dropwise over 5 hours and stirred for another 2 hours. After that, the mixture was cooled to room temperature to obtain polyester (i-1). The number of repeating units of lactone calculated from the raw material charging ratio is 15. The number of repeating units of lactone corresponds to b11 in formula 11 or b21 in formula 12. 2.4 g of polyethyleneimine (SP-006 manufactured by Nippon Shokubai Co., Ltd., number average molecular weight 600), 95 g of polyester (i-1), and 5.0 g of the above-mentioned compound S-1 (siloxane carboxylic acid) were mixed and heated at a temperature of 110° C. for 3 hours to obtain polyalkyleneimine polymer Q-1. 1 H-NMR (Nuclear Magnetic Resonance) and 13 From the results of both C-NMR and C-NMR analyses, it was confirmed that a polymer having the following structural units was obtained.
[0201] [ka]
[0202] <Synthesis of polyalkyleneimine polymer Q-2> Polyalkyleneimine polymer Q-2 was synthesized in the same manner as described above for the synthesis of polyalkyleneimine polymer Q-1, except that compound S-1 was replaced with compound S-2 (siloxane carboxylic acid) shown above. 1 H-NMR and 13 From the results of both C-NMR and C-NMR analyses, it was confirmed that polymers having the following structural units were obtained. The formation of the salt-bridged structures shown below in polymers Q-1 and Q-2 was confirmed from the acid values of polymers Q-1 and Q-2. Oxidation measurements were performed by the method described below. The measured acid values were the values shown in Table 2 below.
[0203] [ka]
[0204] (Acid value measurement method) The acid value (the number of mmol of potassium hydroxide required to neutralize 1 g of sample) was measured by potentiometry (solvent: tetrahydrofuran / water = 100 / 10 (volume ratio), titrant: 0.01 N (0.01 mol / L) potassium hydroxide).
[0205] The weight average molecular weight and number average molecular weight shown above or in the tables below are values measured by GPC under the following measurement conditions and calculated in terms of standard polystyrene.
[0206] (Conditions for measuring weight-average molecular weight of polymers P-1 to P-4 and polyester (i-1)) Measuring instrument: HLC-8220GPC (Tosoh Corporation) Column: TSKgel Super HZ 2000 / TSKgel Super HZ 4000 / TSKgel Super HZ-H (Tosoh Corporation) Eluent: tetrahydrofuran (THF) Flow rate: 0.35mL / min Column temperature: 40℃ Detector: Refractive Index (RI) detector
[0207] (Measurement conditions for weight average molecular weight of polymers Q-1 and Q-2 and number average molecular weight of polyethyleneimine) Measuring instrument: HLC-8320GPC (Tosoh Corporation) Column: 3 TSKgel Super AWM-H (Tosoh Corporation) Eluent: N-methyl-2-pyrrolidone (with 10 mM lithium bromide as an additive) Flow rate: 0.35mL / min Column temperature: 40℃ Detector: RI detector
[0208] The polyalkyleneimine polymer A described below is a polyalkyleneimine polymer synthesized as described above for the synthesis of polyalkyleneimine polymer Q-1, except that 100 g of polyester (i-1) was used without using compound S-1 (siloxane carboxylic acid). The weight average molecular weight of polyalkyleneimine polymer A was measured by GPC under the above-mentioned measurement conditions described for polymer Q-1, etc., and calculated as a standard polystyrene equivalent, and was found to be 7000. For polyalkyleneimine polymer A, 1 H-NMR and 13 From the results of both C-NMR and C-NMR analyses, it was confirmed that a polymer having the following structural units was obtained.
[0209] [ka]
[0210] [Example 1] <Preparation of Magnetic Layer-Forming Composition> The following ingredients were mixed in an open kneader and then dispersed in a sand mill. Ferromagnetic powder: 100.0 parts Polyalkyleneimine polymer A: 10.0 parts Polyurethane resin: (Vylon (registered trademark) UR4800 manufactured by Toyobo Co., Ltd., functional group: SO3Na, functional group concentration: 70eq / ton): 4.0 parts Polyvinyl chloride resin (Kaneka MR104): 10.0 parts Methyl ethyl ketone: 150.0 parts Cyclohexanone: 150.0 parts α-Al2O3 (average particle size 0.1μm): 6.0 parts Carbon black (average particle size: 20 nm): 0.7 parts
[0211] The following components were added to the dispersion obtained above, and the mixture was stirred, then ultrasonically treated and filtered using a filter having a pore size of 1 μm to prepare a composition for forming a magnetic layer. Polymer P-1: 1.5 parts Stearic acid: 1.5 parts Butyl stearate: 0.5 parts Stearic acid amide: 0.3 parts Methyl ethyl ketone: 110.0 parts Cyclohexanone: 110.0 parts Polyisocyanate compound (Tosoh Coronate 3041): 3.0 parts
[0212] <Preparation of composition for forming nonmagnetic layer> The following components were kneaded in an open kneader and then dispersed using a sand mill. The resulting dispersion was filtered using a filter with a pore size of 1 μm to prepare a composition for forming a nonmagnetic layer. Carbon black: 100.0 parts DBP (Dibutyl phthalate) oil absorption: 100mL / 100g pH:8 BET (Brunauer-Emmett-Teller) specific surface area: 250m 2 / g Volatile content: 1.5% Polyurethane resin (Vylon UR4800 manufactured by Toyobo Co., Ltd., functional group: SO3Na, functional group concentration: 70eq / ton): 20.0 parts Vinyl chloride resin (functional group: OSO3K, functional group concentration: 70eq / ton): 30.0 parts Trioctylamine: 4.0 parts Cyclohexanone: 140.0 parts Methyl ethyl ketone: 170.0 parts Stearic acid amide: 0.3 parts Toluene: 3.0 parts Polyisocyanate compound (Tosoh Coronate 3041): 5.0 parts
[0213] <Preparation of Composition for Forming Backcoat Layer> The following components were pre-mixed in a roll mill and then dispersed in a sand mill. To the resulting dispersion, 4.0 parts of polyester resin (Vylon 500 manufactured by Toyobo Co., Ltd.), 14.0 parts of polyisocyanate compound (Coronate 3041 manufactured by Tosoh Corporation) and 5.0 parts of α-Al2O3 (manufactured by Sumitomo Chemical Co., Ltd.) were added, stirred and then filtered to prepare a composition for forming a backcoat layer. Carbon black (average particle size 40 nm): 85.0 parts Carbon black (average particle size 100 nm): 3.0 parts Nitrocellulose: 28.0 parts Polyurethane resin: 58.0 parts Copper phthalocyanine dispersant: 2.5 parts Nipolan 2301 (Tosoh Corporation): 0.5 parts Methyl isobutyl ketone: 0.3 parts Methyl ethyl ketone: 860.0 parts Toluene: 240.0 parts
[0214] <Magnetic recording medium production> Both surfaces of a biaxially oriented polyethylene naphthalate support having a thickness of 5.0 μm were subjected to a corona discharge treatment. The non-magnetic layer forming composition was applied onto one surface of the polyethylene naphthalate support so that the non-magnetic layer had a dry thickness of 1.0 μm, and immediately thereafter, the magnetic layer forming composition was simultaneously applied thereon in a multi-layer manner so that the magnetic layer had a dry thickness of 100 nm. While both layers were in a wet state, a vertical orientation treatment was performed using a cobalt magnet having a magnetic force of 0.5 T (tesla) and a solenoid having a magnetic force of 0.4 T, and then a drying treatment was performed. Then, the backcoat layer forming composition was applied onto the other surface of the polyethylene naphthalate support so that the backcoat layer had a dry thickness of 0.5 μm, and then calendering was performed at a speed of 80 m / min with a calender roll surface temperature of 100° C. using a seven-stage calender consisting of metal rolls. Then, the sheet was slit into a width of 1 / 2 inch (1 inch is 0.0254 meters) to prepare a magnetic tape.
[0215] [Examples 2 to 6, Comparative Examples 1 and 2] A magnetic tape was prepared by the method described in Example 1, except that the polymer P-1 was changed to a polymer shown in Table 1 or Table 2 below.
[0216] [Evaluation method] <Contact angle> For each of the magnetic tapes of the Examples and Comparative Examples, the contact angle was determined by the method described above. More specifically, the contact angle was determined by the following method. A sample piece having a length of 30 cm was cut out from each of the magnetic tapes of the Examples and Comparative Examples. The contact angle of the magnetic layer surface of the sample piece with water was measured by the following method using a contact angle measuring device (DropMaster700 contact angle measuring device manufactured by Kyowa Interface Science Co., Ltd.) The contact angle was measured in a measurement environment with an atmospheric temperature of 20° C. and a relative humidity of 25%. The above sample piece was placed on a glass slide so that the backcoat layer surface was in contact with the glass slide surface. 2.0 μL of the liquid for measurement (water) was dropped onto the surface of the sample piece (magnetic layer surface), and after visually confirming that the dropped liquid formed a stable droplet, the droplet image was analyzed using the contact angle analysis software FAMAS attached to the contact angle measuring device, and the contact angle between the sample piece and the droplet was measured. The contact angle was calculated using the θ / 2 method. The measurement points were six randomly selected points on the magnetic layer surface, and the contact angle was measured at each of the six points. The arithmetic average of the six measured values thus obtained was taken as the contact angle of the magnetic tape to be measured. Method: Droplet method (θ / 2 method) Droplet recognition: automatic Droplet detection line (distance from needle tip): 50dots Algorithm: Automatic Image Mode: Frame Threshold Level: Automatic
[0217] <Friction> In an environment controlled at an atmospheric temperature of 13°C and a relative humidity of 80%, a magnetic head removed from an IBM LTO (registered trademark) G7 (Linear Tape-Open Generation 7) drive was attached to the tape running system, and a 20 m long magnetic tape was repeatedly run (10,000 cycles) at 4.0 m / s while being unwound from the unwound roll and wound around the take-up roll with a tension of 0.6 N. The frictional force acting on the magnetic head during each of the first and 10,000 cycles was measured using a strain gauge, and the friction coefficient μ value was calculated from the measured frictional force. The friction coefficient after repeated runs was evaluated from the measured μ value according to the following evaluation criteria. Evaluation results of A or B are preferable, with A being the most preferable. (Evaluation Criteria) A: μ value is less than 0.08 B: μ value is 0.08 or more and 0.12 or less C: μ value is greater than 0.12
[0218] <5 nm protrusion reduction rate (evaluation of changes in the surface shape of the magnetic layer before and after repeated running)> For each of the magnetic tapes in the Examples and Comparative Examples, the number of protrusions having a height of 5 nm or more on the magnetic layer surface was determined by the following method for the magnetic tape before running and for the magnetic tape after repeated running in the above environment. The number of protrusions with a height of 5 nm or more is determined by measurement using an atomic force microscope (AFM). More specifically, in a planar image of the magnetic layer surface obtained by AFM, the surface where the volume of the convex and concave components in the measurement area is equal is defined as the reference plane, and the number of protrusions with a height of 5 nm or more from this reference plane is determined. Note that among the protrusions with a height of 5 nm or more that exist in the measurement area, there may be some that are partly within the measurement area and other parts that are outside the measurement area. When determining the number of protrusions, the number of protrusions including such protrusions is measured. The measurement area for AFM measurements is a 5 μm square (5 μm x 5 μm) area on the magnetic layer surface. Measurements are performed in three different measurement areas on the magnetic layer surface (n=3). The number of protrusions with a height of 5 nm or more is calculated as the arithmetic mean of the three values obtained by such measurements. The following measurement conditions are used for AFM measurements. An AFM (Veeco's Nanoscope 4) is used in tapping mode to measure a 5 μm square (5 μm × 5 μm) area on the surface of the magnetic layer of the magnetic tape. A BRUKER's RTESP-300 is used as the probe, with a resolution of 512 pixels × 512 pixels and a scan speed of 341 seconds per screen (512 pixels × 512 pixels). The change in the surface shape of the magnetic layer before and after repeated running was evaluated according to the following evaluation criteria using the protrusion reduction rate calculated by the following formula: The smaller the protrusion reduction rate, the more suppressed the change in the surface shape of the magnetic layer before and after repeated running can be judged to be. Protrusion reduction rate (%)=[(protrusion number found on unrun magnetic tape)−(protrusion number found on magnetic tape after the above repeated running) / (protrusion number found on unrun magnetic tape)]×100 (Evaluation Criteria) A: Protrusion reduction rate is 40% or less B: Protrusion reduction rate is more than 40% and less than 70% C: Protrusion reduction rate is 70% or more
[0219] The above results are shown in Tables 1 and 2.
[0220] [Table 1]
[0221] [Table 2]
[0222] [Example 7] A magnetic tape was produced by the method described in Example 1, except that instead of using 10.0 parts of polymer P-1, 2.0 parts of polyalkyleneimine-based polymer A was used as the nitrogen-containing raw polymer, and 0.5 parts of compound S-1 (siloxane carboxylic acid) shown above was used as the silicon-containing raw compound. The magnetic tape obtained was evaluated by the method described above.
[0223] [Example 8] A magnetic tape was prepared by the method described in Example 7, except that compound S-1 was replaced with compound S-2 (siloxane carboxylic acid) shown above. The obtained magnetic tape was evaluated by the method described above.
[0224] The above results are shown in Table 3.
[0225] [Table 3]
[0226] From the results shown in Tables 1 to 3, it can be confirmed that the magnetic tapes of Examples 1 to 8 have a low friction coefficient after repeated running, and there is little change in the surface shape of the magnetic layer before and after repeated running. [Industrial Applicability]
[0227] One aspect of the present invention is useful in the technical field of magnetic recording media for high density recording.
Claims
1. A magnetic recording medium having a non-magnetic support and a magnetic layer containing ferromagnetic powder, The non-magnetic support contains a silicon-containing compound having a partial structure represented by the following formula 1 in a portion on the magnetic layer side thereof: 【Chemistry 1】 In formula 1, R 11 , R 12 and R 13 each independently represents a monovalent substituent; L 11 represents a (n+1)-valent linking group, n represents an integer of 2 or more, and * represents the position at which the partial structure represented by formula 1 is bonded to another partial structure constituting the silicon-containing compound.
2. The silicon-containing compound is a polymer having a structural unit represented by the following formula 2: 【Chemistry 2】 In formula 2, R 21 and R 22 each independently represents a hydrogen atom or an alkyl group; R 23 represents a hydrogen atom or a monovalent substituent; L 12 represents a single bond or a divalent linking group, * represents the position at which the structural unit represented by formula 2 is bonded to another partial structure constituting the silicon-containing compound, R 11 , R 12 , R 13 , L 11 and n are R in Formula 1, 11 , R 12 , R 13 , L 11 2. The magnetic recording medium according to claim 1, wherein n is defined as n and n is defined as n.
3. In formula 2, R 21 and R 22 represents a hydrogen atom, R 23 3. The magnetic recording medium according to claim 2, wherein represents a hydrogen atom or a methyl group.
4. The constitutional unit represented by formula 2 is a constitutional unit represented by the following formula 3: 【Chemistry 3】 In formula 3, R 23 represents a hydrogen atom or a methyl group, * represents the position at which the structural unit represented by formula 3 is bonded to another partial structure constituting the silicon-containing compound, R 11 , R 12 , R 13 , L 11 and n are R in Formula 1, 11 , R 12 , R 13 , L 11 and n are synonymous with each other.
5. 3. The magnetic recording medium according to claim 2, wherein the polymer contains at least one selected from the group consisting of a carboxy group, an amino group, a hydroxy group, a sulfo group, a phosphonoxy group and salts thereof, an alkyl group, a glycol structure, an ester structure, an amide structure, an anionic structure, and an amphoteric structure.
6. 3. The magnetic recording medium according to claim 2, wherein the polymer contains at least one selected from the group consisting of a carboxy group, an amino group, a hydroxy group, a sulfo group, a phosphonoxy group and salts thereof, an alkyl group, and a glycol structure.
7. 3. The magnetic recording medium according to claim 2, wherein the polymer contains at least one selected from the group consisting of a carboxy group, an amino group, a hydroxy group, a sulfo group, a phosphonoxy group, and salts thereof, an ester structure, and an amide structure.
8. 3. The magnetic recording medium according to claim 2, wherein the weight average molecular weight of the polymer is 2,000 or more and less than 200,000. Magnetic recording media.
9. The polymer contains at least one selected from the group consisting of a carboxy group, an amino group, a hydroxy group, a sulfo group, a phosphonoxy group, and salts thereof, an ester structure, and an amide structure; and 5. The magnetic recording medium according to claim 4, wherein the weight average molecular weight of the polymer is 2,000 or more and less than 200,000.
10. The magnetic recording medium of claim 1 , wherein the silicon-containing compound is a nitrogen-containing polymer.
11. The magnetic recording medium according to claim 10, wherein the nitrogen-containing polymer is a polyalkyleneimine-based polymer.
12. The magnetic recording medium of claim 10, wherein the nitrogen-containing polymer further comprises a polyester chain.
13. 11. The magnetic recording medium according to claim 10, wherein the nitrogen-containing polymer has a weight average molecular weight of 4,000 or more and less than 20,000.
14. the nitrogen-containing polymer is a polyalkyleneimine-based polymer, The polyalkyleneimine-based polymer further has a polyester chain, and 11. The magnetic recording medium according to claim 10, wherein the weight average molecular weight of the polyalkyleneimine polymer is 4,000 or more and less than 20,000.
15. 2. The magnetic recording medium according to claim 1, wherein the contact angle with water measured on the surface of the magnetic layer is 90[deg.] or more.
16. 2. The magnetic recording medium according to claim 1, further comprising at least one fatty acid compound selected from the group consisting of fatty acids, fatty acid esters and fatty acid amides, on the portion of the non-magnetic support on the side of the magnetic layer.
17. 2. The magnetic recording medium according to claim 1, further comprising a non-magnetic layer containing a non-magnetic powder between the non-magnetic support and the magnetic layer.
18. 2. The magnetic recording medium according to claim 1, further comprising a backcoat layer containing a nonmagnetic powder on the surface of said nonmagnetic support opposite to the surface having said magnetic layer.
19. 2. The magnetic recording medium according to claim 1, which is a magnetic tape.
20. the contact angle with water measured on the surface of the magnetic layer is 90° or more; the non-magnetic support further contains at least one fatty acid compound selected from the group consisting of fatty acids, fatty acid esters, and fatty acid amides in a portion on the magnetic layer side of the non-magnetic support, a non-magnetic layer containing a non-magnetic powder between the non-magnetic support and the magnetic layer, a backcoat layer containing a nonmagnetic powder on the surface side of the nonmagnetic support opposite to the surface side having the magnetic layer; and 10. The magnetic recording medium according to claim 9, which is a magnetic tape.
21. the contact angle with water measured on the surface of the magnetic layer is 90° or more; the non-magnetic support further contains at least one fatty acid compound selected from the group consisting of fatty acids, fatty acid esters, and fatty acid amides in a portion on the magnetic layer side of the non-magnetic support, a non-magnetic layer containing a non-magnetic powder between the non-magnetic support and the magnetic layer, a backcoat layer containing a nonmagnetic powder on the surface side of the nonmagnetic support opposite to the surface side having the magnetic layer; and The magnetic recording medium according to claim 14, which is a magnetic tape.
22. A magnetic tape cartridge comprising the magnetic tape according to any one of claims 19 to 21.
23. A magnetic recording and reproducing device comprising the magnetic recording medium according to any one of claims 1 to 21.
Citation Information
Patent Citations
Magnetic recording medium and its production
JP1998261220A
magnetic recording medium
JP4070147B1